Preparation and use of molecular sieve intergrowth of cha and aft with "sfw-gme tail"

The development of JMZ-11 molecular sieves with interlinked CHA and AFT crystals and a 'sfw-GME tail' addresses the need for enhanced catalytic properties, achieving improved catalytic activity and adaptability in exhaust gas treatment.

JP7664841B2Active Publication Date: 2025-04-18JOHNSON MATTHEY PLC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021549837
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-28
Filing Date
2020-03-27
Publication Date
2025-04-18
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

There is a need for new molecular sieves with known basic structures that can enhance one or more catalytic properties with slight changes in their structure, which may not be discernible using common analytical techniques.

Method used

A family of molecular sieves (JMZ-11) containing interlinked CHA and AFT crystals with a 'sfw-GME tail' is developed, which includes four subgroups (JMZ-11A, JMZ-11B, JMZ-11C, and JMZ-11D) with specific compositions and structural directing agents.

Benefits of technology

The JMZ-11 molecular sieves exhibit improved catalytic activity compared to closely related zeolites, allowing for better adaptation of exhaust gas composition to regulatory requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664841000023
    Figure 0007664841000023
  • Figure 0007664841000024
    Figure 0007664841000024
  • Figure 0007664841000025
    Figure 0007664841000025
Patent Text Reader

Abstract

A molecular sieve is described that includes an intergrowth of cha and aft with an "sfw-GME tail," at least one structure directing agent (SDA) within the molecular sieve framework, an intergrowth of the CHA framework and the GME framework, cha cavities, and aft cavities. A first SDA containing either an N,N-dimethyl-3,5-dimethylpiperidinium cation or an N,N-diethyl-2,6-dimethylpiperidinium cation is required. A second SDA, which may be present, is either a CHA or an SFW-generating cation. The amount of second SDA-2 used can vary the ratio of components in the cha-aft-"sfw-GME tail." Activated molecular sieves formed from SDA-containing molecular sieves are described. Compositions for preparing these molecular sieves are described. Methods for preparing SDA-containing JMZ-11, activated JMZ-11, and metal-containing activated JMZ-11 are described. Methods for using activated JMZ-11 and metal-containing activated JMZ-11 in various processes such as exhaust gas treatment and methanol to olefins conversion are described.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to molecular sieves comprising an intergrowth of cha and aft with an "sfw-GME tail". These molecular sieves include as-prepared molecular sieves containing one or more structure directing agents (SDAs), as well as activated molecular sieves, which do not contain SDA and may be formed from SDA-containing molecular sieves. The present invention also relates to methods for preparing the SDA-containing and activated molecular sieves, and methods for using these activated molecular sieves as catalysts. [Background technology]

[0002] Molecular sieves are a commercially important class of materials that have a well-defined crystal structure with a defined pore structure as shown by a well-defined X-ray diffraction (XRD) pattern. The crystal structure defines the cavities and channels / pores that are characteristic of a particular type of molecular sieve. This is usually described as a framework type or topological type. A complete list of framework types is maintained by IZA (International Zeolite Association) http: / / www.iza-structure.org / databases / . Such framework types or topological types are not defined by composition but only by the arrangement of T-atoms (tetrahedral atoms) that connect the channels / pores and cavities to make up the structure. Framework types or topological types are unique and are assigned a unique three-letter code by IZA.

[0003] During the formation and growth of molecular sieve crystals, defects may occur that can initiate the growth of various structures within the bulk material. This may result in the appearance of distinct phases recognized by XRD. The distinct phases may be referred to as disordered structures or intergrowths. Disordered structures are defined as structures with periodic order in less than three dimensions, such as two, one, or zero dimensions. This phenomenon is also referred to as stacking disorder of structurally invariant periodic building units (PerBUs). In other words, a disordered structure is one in which the stacking arrangement of PerBUs deviates from periodic order to a random stacking arrangement. Chemical disorder (i.e., different cations on specific sites), dynamic disorder (i.e., rotational disorder of template molecules), and structural disorder (i.e., disordered molecules in the cavities of the zeolite framework) are excluded from this definition. The physicochemical properties and catalytic behavior of disordered structures may differ from those of their ordered counterparts. For example, CHA / AEI (M. Janssen, A. Verberckmoes, M. Mertens, A. Bons, W. Mortier, ExxonMobile Chemical Europe Inc. European Patent No. 1 365 992 (B1), 2007) is composed of double 6-membered ring layers. W. Slawinski, D. S. Ragg, D. Akporiaye, H. Fjellvag, Microporous Mesoporous Mater., 2014, 195, 311-318), EMT / FAU composed of sod cages linked through double T6 rings in hexagonal layers (JM Newsam, MM J Treacy, DEW Vaughan, KG Strohmaier, WJ Mortier, Chem. Commun., 1989, 493-495), T9 units: i.e. LOV / VSV / RSN composed of two 4-rings connected through a single T atom related by pure translation along the a- and b-axes (S. Merlino, Eur. J. Miner., 1990, 2, 809-817. C. Rohrig, H. Gies, B. Marler, Zeolites, 1994, 14, 498-503).C. Rohrig, H. Gies, Angew. Chem. Int. Ed. Engl., 1995, 34, 63-65). Further examples of disorder in zeolite frameworks are reported in the database of zeolite structures (http: / / europe.iza-structure.org / IZA-SC / intergrowth_Table.html). The synthesis conditions, the nature of the metal cations, the shape and size of the SDA used to synthesize structures belonging to a given family can affect the regular arrangement of the building units, leading to the formation of intergrowth and stacking disordered structures.

[0004] The new intergrowth zeolites described herein are related to the ABC-6 family of structures, specifically those containing only double 6-rings (D6R) (http: / / europe.iza-structure.org / IZA-SC / intergrowth_families / ABC_6.pdf). The ABC-6 structure is built up from 6R with different stacking arrangements along one axis and connected by 4R. The 6R units can be centered at three different positions along the hexagonal ab plane: A (0,0,0), B (2 / 3,1 / 3,0) and C (1 / 3,2 / 3,0).

[0005] Molecular sieves that have been synthesized and identified as members of the disordered ABC-6 family consisting of only double hexacyclic rings include ZK-14 [GH Kuehl. In: Molecular Sieves SCI, London, 1967, p85]; Babelite [R. Szostak and KP Lillerud, J. Chem. Soc. Chem. Commun. 1994, (20), 2357-2358]; Linde D [KP Lillerud, R. Szostak and A. Long, J. Chem. Soc. Faraday Trans. 1994, 90, 1547-1551; UK Patent No. 868,649]; Phi [KP Lillerud, R. Szostak and A. Long, J. Chem. Soc. Faraday Trans. 1994, 90, 1547-1551; UK Patent No. 868,649]; Trans. 1994, 90, 1547-1551; U.S. Patent No. 4,124,668]; LZ-276 [GW Skeels, M. Sears, CA Bateman, NK McGuire, EM Flanigen, M. Kumar, RM Kirchner, Micropor. Mesopor. Mater. 30, 335 (1999); U.S. Patent No. 5,248,491]; LZ-277 [GW Skeels, M. Sears, CA Bateman, NK McGuire, EM Flanigen, M. Kumar, RM Kirchner, Micropor. Mesopor. Mater. 30, 335 (1999); U.S. Patent No. 5,192,522]; SAPO AFX / CHA [U.S. Patent No. 7,906,099]; SSZ-52 [D. Xie, L.B. McCusker, C. Baerlocher, SIZones, W. Wan, X. Zou, J. Am. Chem. Soc. 2013, 135(28), 10519-24; U.S. Patent No. 6,379,531]; ZTS-1 and ZTS-2 [Y. Naraki, K. Ariga, K. Nakamura, K. Okushita, T. Sano, Microporous Mesoporous Mater. (2017) 254, 160-169; JP 2017065943]; defective CHA-type zeolites [J. Kim, DH Kim, Microporous Mesoporous Mater.2018, 256, 266-274]; defective GME [U.S. Patent No. 9,643,853]; SSZ-52x [U.S. Patent No. 10,150,676]; and GME / CHA [WO 2018 / 086974].

[0006] WO 2018 / 086974 discloses a method for preparing a series of zeolites belonging to the ABC-6 framework family in which the ABC stacking sequence is disordered and the silica to alumina ratio is in the range of 8 to 60. According to the diffraction peaks in claim 3 and the related examples reported, these zeolites can be classified as stochastic CHA-GME intergrowth.

[0007] Molecular sieves have many industrial applications, and certain framework molecular sieves, such as CHA, are known to be effective catalysts for treating combustion exhaust gases in industrial applications including internal combustion engines, gas turbines, and coal-fired power plants. In one example, they can be used to reduce nitrogen oxides (NO x ) can be controlled by the so-called selective catalytic reduction (SCR) process, whereby NO x The compound is contacted with a reducing agent in the presence of a zeolite catalyst. In another example, molecular sieves having a CHA framework type find application in methanol to olefins (MTO) catalysis. Summary of the Invention [Problem to be solved by the invention]

[0008] There is a need to develop new molecular sieves that have the basic structure of known molecular sieves, but whose slight changes in structure can affect one or more of the catalytic properties of the molecular sieve. In some cases, the slight changes in structure may not be discernible using commonly used analytical techniques, but the catalytic activity of the structurally modified zeolite may be improved compared to a closely related analogous zeolite. This unexpected improvement in the catalytic activity of structurally modified molecular sieves may allow the composition of exhaust gases from engines to meet various regulatory requirements.

[0009] In a first aspect of the present invention, there is provided a family of molecular sieves (JMZ-11) comprising an intergrowth of cha and aft having an "sfw-GME tail", which molecular sieve comprises one or more structure directing agents, hereinafter referred to as "the molecular sieve" or "these molecular sieves". The "sfw-GME tail" can be identified by analysis using the Reichweite 2 DIFFaX model.

[0010] Four subgroups of the JMZ-11 family of molecular sieves including these intergrowths, namely JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D, are described below.

[0011] JMZ-11A comprises a structure directing agent (SDA-1) which is an N,N-dimethyl-3,5-dimethylpiperidinium cation, a cha cavity, an aft cavity and an "sfw-GME" tail, where the cha cavity is present in about 45 to about 65%, preferably about 54%, of the cavities in the "sfw-GME" tail, the aft cavity is present in about 18 to about 28%, preferably about 23%, of the cavities in the "sfw-GME" tail, and the remainder is present in about 7 to about 37%, preferably about 23%, of the larger cavities in the "sfw-GME" tail. The aft cavity and the gme cavity associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 35 to about 80%, preferably about 68%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11A has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0012] JMZ-11B comprises a structure directing agent (SDA-1) which is an N,N-diethyl-2,6-dimethylpiperidinium cation, a cha cavity, an aft cavity and an "sfw-GME" tail, where the cha cavity is present in about 55 to about 75%, preferably about 65%, of the cavities in the "sfw-GME" tail, the aft cavity is present in about 0 to about 10%, preferably about 5%, of the cavities in the "sfw-GME" tail, and the remainder is present in about 15 to about 45%, preferably about 30%, of the larger cavities in the "sfw-GME" tail. The aft cavity and the gme cavity associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 40 to 80%, preferably about 64%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11B has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0013] JMZ-11C contains two structure directing agents, N,N-dimethyl-3,5-dimethylpiperidinium cation and 1,3-bis(1-adamantyl)imidazolium cation, cha cavities, aft cavities and an "sfw-GME" tail, where the cha cavities are present in about 30 to about 45%, preferably about 39%, of the cavities in the "sfw-GME" tail, the aft cavities are present in about 45 to about 65%, preferably about 54%, of the cavities in the "sfw-GME" tail, and the remainder are present in about 2 to about 20%, preferably about 7%, of the larger cavities in the "sfw-GME" tail. The aft cavities and the gme cavities associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 5 to 45%, preferably about 23%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11C has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0014] JMZ-11D contains two structure directing agents, N,N-dimethyl-3,5-dimethylpiperidinium cation and trimethylamandylammonium cation, cha cavities, aft cavities and an "sfw-GME" tail, where the cha cavities are present in about 55 to about 75%, preferably about 65%, of the cavities in the "sfw-GME" tail, the aft cavities are present in about 7 to about 17%, preferably about 12%, of the cavities in the "sfw-GME" tail, and the remainder are present in about 8 to about 38%, preferably about 23%, of the larger cavities in the "sfw-GME" tail. The aft cavities and the gme cavities associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 50 to 90%, preferably about 75%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11D has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0015] The molecular sieves described herein can be an aluminosilicate or a metal substituted aluminosilicate. Preferably, the molecular sieve is an aluminosilicate.

[0016] These molecular sieves can include phosphorus in the framework. These molecular sieves can be aluminophosphates (AlPO), metal-substituted aluminophosphates (MeAlPO), silicoaluminophosphates (SAPO), or metal-substituted silicoaluminophosphates.

[0017] These molecular sieves can include at least one metal in the framework, the metal being from one of groups IIIA, IB, IIB, VA, VIA, VIIA, VIIIA of the periodic table, and combinations thereof. Preferably, the metal is one or more of cerium, chromium, cobalt, copper, iron, magnesium, manganese, molybdenum, nickel, palladium, platinum, rhodium, titanium, tungsten, vanadium, and zinc. More preferably, the metal is one or more of cobalt, copper, iron, manganese, and zinc.

[0018] In a second aspect of the present invention, the activated H-form of the molecular sieve of the first aspect of the present invention, hereinafter referred to as "activated molecular sieve" or "these activated molecular sieves", is described.

[0019] These molecular sieves in the activated H form can be aluminosilicates or metal-substituted aluminosilicates. Preferably, these molecular sieves in the activated H form are aluminosilicates.

[0020] The activated H-forms of these molecular sieves can contain phosphorus in the framework. These activated H-forms of these molecular sieves can be aluminophosphates (AlPO), metal-substituted aluminophosphates (MeAlPO), silicoaluminophosphates (SAPO), or metal-substituted silicoaluminophosphates.

[0021] These molecular sieves in the activated H form can include at least one metal in the framework, which metal is selected from one of the metals of groups IIIA, IB, IIB, VA, VIA, VIIA, and VIIIA of the periodic table, and combinations thereof. Preferably, the metal is cerium, chromium, cobalt, copper, iron, magnesium, manganese, molybdenum, nickel, palladium, platinum, rhodium, titanium, tungsten, vanadium, or zinc. More preferably, the metal is cobalt, copper, iron, manganese, or zinc.

[0022] These molecular sieves in the activated H form can contain at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn, preferably Cu, Fe, Co and Ni, more preferably Cu and Fe, and most preferably Cu.

[0023] In a third aspect of the invention, the catalyst comprises the activated H-form of one or more of the molecular sieves of the second aspect of the invention and at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn, preferably Cu, Fe, Co and Ni, more preferably Cu and Fe, most preferably Cu.

[0024] The activated H-type molecular sieve in the catalyst can contain from about 0.1 to about 5 weight percent of at least one extraframework metal.

[0025] These molecular sieves in the activated H form can be aluminosilicates or metal-substituted aluminosilicates, preferably aluminosilicates.

[0026] The activated H-type of these molecular sieves can contain phosphorus in the framework. These activated H-type of these molecular sieves can be aluminophosphates (AlPO), metal-substituted aluminophosphates (MeAlPO), silicoaluminophosphates (SAPO), or metal-substituted silicoaluminophosphates.

[0027] These molecular sieves in the activated H form can include at least one metal in the framework, which metal is selected from at least one of the metals of groups IIIA, IB, IIB, VA, VIA, VIIA and VIIIA of the periodic table, and combinations thereof. Preferably, the metal is one or more of cerium, chromium, cobalt, copper, iron, magnesium, manganese, molybdenum, nickel, palladium, platinum, rhodium, titanium, tungsten, vanadium and zinc, more preferably cobalt, copper, iron, manganese and zinc.

[0028] In a fourth aspect of the present invention, a catalyst article for treating exhaust gases comprises a catalyst comprising one or more of the activated H-form molecular sieves of the second aspect of the present invention and at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn, preferably Cu, Fe, Co and Ni, more preferably Cu and Fe, and most preferably Cu.

[0029] These molecular sieves in the activated H form in the catalyst can contain from about 0.1 to about 5 weight percent of at least one extraframework metal.

[0030] The catalyst may be disposed on and / or within a porous substrate, preferably a flow-through filter or a wall-flow filter.

[0031] In a fifth aspect of the invention, a system for treating exhaust gases produced by a combustion process, such as, for example, by an internal combustion engine (whether mobile or stationary), a gas turbine, a coal or oil fired power plant, etc., comprises a catalytic article comprising one or more activated H-forms of the molecular sieve of the second aspect of the invention and at least one extraframework metal. Such a system comprises a catalytic article comprising an activated molecular sieve as described herein and may also include at least one additional component for treating the exhaust gases, the catalytic article and the at least one additional component being designed to function as a coherent unit.

[0032] An exhaust system for treating exhaust gases from an engine may include (a) a catalyst article comprising one or more activated H-forms of one or more of the molecular sieves of the second aspect of the invention and at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn, preferably Cu, Fe, Co and Ni, more preferably Cu and Fe, most preferably Cu, disposed downstream from the engine, (b) a source of a reducing agent, such as ammonia or urea, upstream of the catalyst article, and (c) an exhaust gas conduit for conveying exhaust gases from the engine to the catalyst article.

[0033] In some embodiments, these molecular sieves in the activated H form can be the SCR or ammonia oxidation component.

[0034] The system may include a catalytic article including one or more of these molecular sieves or one or more of the metal-containing activated molecular sieves, a conduit for conducting the flowing exhaust gas, and a source of nitrogenous reductant disposed upstream of the catalytic article. The system may be configured to detect whether the one or more activated molecular sieves or the one or more metal-containing activated molecular sieves are capable of reducing NO at or above a desired efficiency over a specified temperature range, such as above 100° C., above 150° C., or above 175° C. xA controller may be included for metering nitrogenous reductant into the flowing exhaust gas only when it is determined that the nitrogenous reductant can catalyze the reduction. The metering of the nitrogenous reductant may be adjusted so that 60% to 200% of the theoretical ammonia is present in the exhaust gas entering the SCR catalyst, calculated at 1:1 NH3 / NO and 4:3 NH3 / NO2.

[0035] The system may include an oxidation catalyst (e.g., a diesel oxidation catalyst (DOC)) for oxidizing nitric oxide in the exhaust gas to nitrogen dioxide, which may be located upstream of where the nitrogenous reductant is metered into the exhaust gas. The oxidation catalyst may be adapted to produce a gas stream entering the SCR molecular sieve catalyst having a NO to NO2 volume ratio of about 4:1 to about 1:3, for example, at an exhaust gas temperature at the oxidation catalyst inlet of 250°C to 450°C. The oxidation catalyst may include at least one platinum group metal (or some combination thereof), such as platinum, palladium, or rhodium, coated on a flow-through monolith substrate. The at least one platinum group metal may be platinum, palladium, or a combination of both platinum and palladium. The platinum group metal may be supported on a high surface area washcoat component, such as alumina, zeolite, silica, non-zeolitic silica alumina, ceria, zirconia, titania, or mixed or composite oxides containing both ceria and zirconia.

[0036] A suitable filter substrate may be located between the oxidation catalyst and the SCR catalyst. The filter substrate may be selected from any of those described above, for example a wall-flow filter. If the filter is catalyzed, for example with an oxidation catalyst of the type described above, then the metering point for the nitrogenous reductant is preferably located between the filter and the molecular sieve catalyst. Alternatively, if the filter is not catalyzed, the means for metering the nitrogenous reductant may be located between the oxidation catalyst and the filter.

[0037] In a sixth aspect of the present invention, a method for synthesizing the SDA-containing molecular sieve of the first aspect of the present invention comprises the steps of: a. forming a reaction mixture comprising: (i) at least one aluminum source; (ii) at least one silicon source; (iii) at least one alkali or alkaline earth cation source; and (iv) one or more structure directing agents; b. heating the reaction mixture; c. forming molecular sieve crystals having intergrowths and a structure directing agent as described herein; d. Recovering at least a portion of the molecular sieve crystals from the reaction mixture.

[0038] The SDA for JMZ-11A contains an N,N-dimethyl-3,5-dimethylpiperidinium cation. The SDA for JMZ-11B contains an N,N-diethyl-2,6-dimethylpiperidinium cation. The SDA for JMZ-11C contains an N,N-dimethyl-3,5-dimethylpiperidinium cation and a 1,3-bis(1-adamantyl)imidazolium cation. The SDA for JMZ-11D contains an N,N-dimethyl-3,5-dimethylpiperidinium cation and a trimethyladamantylammonium cation.

[0039] The at least one aluminum source can include aluminum alkoxides, aluminum phosphate, aluminum hydroxide, sodium aluminate, pseudoboehmite, hydrated alumina, organoalumina, colloidal alumina, zeolite Y, and mixtures thereof.

[0040] The at least one silicon source can be an alkoxide, colloidal silica, silica gel, a silicate, a tetraalkylorthosilicate, or an aqueous colloidal suspension of silica.

[0041] The source of alkali or alkaline earth cations may be any source of these elements, and is preferably selected from sources of Na, K, and combinations thereof.

[0042] The cation of the structure directing agent can be associated with an anion selected from the group consisting of acetate, bicarbonate, bromide, carbonate, carboxylate, chloride, fluoride, hydroxide, iodide, sulfate and tetrafluoroborate. Preferably, the anion is hydroxide.

[0043] The reaction mixture may have the following molar composition:

[0044] [Table 1] where Me is Si, Ge, Sn, Ti or a combination thereof and is calculated to be in the oxide form (MO2), A is Al, Fe, Cr, B, Ga or a combination thereof and is calculated to be in the oxide form (A2O3), X is Na, K or a combination thereof and is calculated to be in the oxide form (X2O), and [OH - is calculated as the sum of hydroxide ions contributed by all components, SDA-1 is N,N-dimethyl-3,5-dimethylpiperidinium cation or N,N-diethyl-2,6-dimethylpiperidinium cation, SDA-2 is CHA-generating SDA, e.g., trimethyladmandylammonium cation, tetraethylammonium cation, trimethylbenzylammonium cation, trimethylcyclohexylammonium cation or trimethyl(cyclohexylmethyl)ammonium or phenanthylammonium cation. and SDA-3 is an AFX-generated SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

[0045] The reaction mixture can further comprise about 0.1 to about 10% w / w of seed crystals, the seed crystals comprising crystalline molecular sieves having an AEI, AFX, AFT, CHA, GME or SFW framework and / or intergrowths having a JMZ-11 framework.

[0046] In a seventh aspect of the present invention, a method is described for synthesizing an activated molecular sieve of the second aspect of the present invention from a molecular sieve containing a structure directing agent (SDA) of the first aspect of the present invention. The activated molecular sieve lacks the structure directing agent present in the molecular sieve of the first aspect of the present invention. The molecular sieve containing the structure directing agent (SDA) can be calcined to remove the SDA by treatment with a compound capable of reacting with, and preferably decomposing, the SDA, such as a peroxide.

[0047] In an eighth aspect of the present invention, a composition for producing the SDA-containing molecular sieve of the first aspect of the present invention comprises the following materials in corresponding proportions:

[0048] The reaction mixture may have the following molar composition:

[0049] [Table 2] where Me is Si, Ge, Sn, Ti or a combination thereof and is calculated to be in the oxide form (MO2), A is Al, Fe, Cr, B, Ga or a combination thereof and is calculated to be in the oxide form (A2O3), X is Na, K or a combination thereof and is calculated to be in the oxide form (X2O), and [OH -is calculated as the sum of hydroxide ions contributed by all components, SDA-1 is N,N-dimethyl-3,5-dimethylpiperidinium cation or N,N-diethyl-2,6-dimethylpiperidinium cation, SDA-2 is CHA-generating SDA, e.g., trimethyladmandylammonium cation, tetraethylammonium cation, trimethylbenzylammonium cation, trimethylcyclohexylammonium cation or trimethyl(cyclohexylmethyl)ammonium or phenanthylammonium cation. and SDA-3 is an AFX-generated SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

[0050] The composition may further comprise from about 0.1 to about 10% w / w of seed crystals comprising crystalline molecular sieves having an AEI, AFX, AFT, CHA, GME or SFW framework and / or intergrowths having a JMZ-11, JMZ-11B or JMZ-11C framework.

[0051] In the ninth aspect of the present invention, there is provided a method for preparing the activated molecular sieve of the second aspect of the present invention from a molecular sieve containing the SDA of the first aspect of the present invention and an alkali metal cation. The molecular sieve of the present invention may be a Na-type zeolite, a K-type zeolite, or a combination of Na,K-type, etc., or may be an H-type zeolite, an ammonium-type zeolite, or a metal-exchanged zeolite. The method for preparing the activated molecular sieve of the second aspect of the present invention from a molecular sieve containing the SDA of the first aspect of the present invention and an alkali metal cation may use a typical ion-exchange technique, which involves contacting the molecular sieve with a solution containing a salt of the desired replacement cation or cations. The ion-exchange is carried out after synthesis, which may be carried out either before or after calcining the molecular sieve.

[0052] In a tenth aspect of the present invention, there is provided a method for treating exhaust gas from an engine by contacting the exhaust gas with an activated molecular sieve of the second aspect of the present invention described herein.

[0053] The method for treating exhaust gases is x and / or NH3-containing combustion exhaust gas is contacted with the activated H-form molecular sieve of the second aspect of the invention described herein to produce NO x to N2 and H2O, and / or oxidizing at least a portion of the NH3.

[0054] A method for treating exhaust gas comprising contacting a combustion exhaust gas containing NOx with a passive NOx sorbent comprising the activated H-form molecular sieve of the second aspect of the present invention as described herein.

[0055] In an eleventh aspect of the present invention, there is provided a process for converting methanol to olefins (MTO) by contacting methanol with the activated H-form of the molecular sieve of the second aspect of the present invention described herein. [Brief description of the drawings]

[0056] [Figure 1] FIG. 1 is a powder XRD pattern of SDA-containing (as-prepared) JMZ-11A with normalized intensity. [Diagram 2] FIG. 2 is a powder XRD pattern of activated (calcined) H-JMZ-11A with normalized intensity. [Diagram 3] FIG. 3 is a powder XRD pattern of SDA-containing (as-prepared) JMZ-11B with normalized intensity. [Figure 4] FIG. 4 is a powder XRD pattern of activated (calcined) H-JMZ-11B with normalized intensity. [Diagram 5] FIG. 5 is a powder XRD pattern of SDA-containing (as-prepared) JMZ-11C with normalized intensity. [Figure 6] FIG. 6 is a powder XRD pattern of activated (calcined) H-JMZ-11C with normalized intensity. [Figure 7] FIG. 7 is a powder XRD pattern of SDA-containing (as-prepared) JMZ-11D with normalized intensity. [Figure 8] FIG. 8 is a powder XRD pattern of activated (calcined) H-JMZ-11D with normalized intensity. [Figure 9] FIG. 9 shows the powder XRD patterns of calcined H-JMZ-11A through H-JMZ11D with normalized intensities shown at 7 to 13 degrees 2-theta. [Figure 10] Figure 10 depicts the CHA construction scheme from IZA. [Figure 11] Figure 11 depicts the GME construction scheme from IZA. [Figure 12] Figure 12 shows the transition probability matrix for Reichweite 0, where the stacking probability of a layer is independent of the previous stacking. [Figure 13]FIG. 13 is the transition probability matrix for Reichweite 1, where a previous 5 Å thick layer influences the stacking probability. [Figure 14] FIG. 14 is a transition probability matrix for the Reichweite 2 description, where the two previous 5 Å thick layers affect the stacking probability. [Figure 15] FIG. 15 shows the cage distribution for a simple stochastic CHA-GME skeletal intergrowth (corresponding to Reichweite 0). [Figure 16] FIG. 16 shows the cage distribution for a simple "block" intergrowth of CHA and GME. [Figure 17] FIG. 17 shows cage distribution for the cha-aft-“sfw-GME” tail intergrowth in Example 1 (JMZ-11A). [Figure 18] Figure 18 shows the cage distribution within JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D. [Figure 19] Figure 19 shows the cage distribution within JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D. [Figure 20] Figure 20 shows the cage distribution within JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D. [Figure 21] Figure 21 shows the cage distribution within JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D. [Figure 22] FIG. 22 shows a comparison of the experimental XRD patterns of activated JMZ-11A, JMZ-11B, JMZ-11C, and JMZ-11D with DIFFaX simulations performed using the Reichweite 2 description. [Diagram 23] FIG. 23 shows a comparison of the experimental XRD patterns of activated JMZ-11A, JMZ-11B, JMZ-11C, and JMZ-11D with DIFFaX simulations performed using the Reichweite 2 description. [Figure 24]FIG. 24 shows a comparison of the experimental XRD patterns of activated JMZ-11A, JMZ-11B, JMZ-11C, and JMZ-11D with DIFFaX simulations performed using the Reichweite 2 description. [Diagram 25] FIG. 25 shows a comparison of the experimental XRD patterns of activated JMZ-11A, JMZ-11B, JMZ-11C, and JMZ-11D with DIFFaX simulations performed using the Reichweite 2 description. [Figure 26] FIG. 26 shows the NOx conversion profile from the fresh JMZ-11 sample impregnated with Cu. [Figure 27] FIG. 27 shows the NOx conversion profile from the Cu-impregnated aged JMZ-11 sample. [Figure 28] FIG. 28 shows the N2O production profile from the fresh JMZ-11 sample impregnated with Cu. [Figure 29] FIG. 29 shows the N2O production profile from the aged JMZ-11 sample impregnated with Cu. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0057] The following terms are used throughout the present specification and have the following meanings unless otherwise stated.

[0058] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a catalyst" includes a mixture of two or more catalysts, and the like.

[0059] The term "about" means approximately and refers to a range, optionally of ±25%, preferably ±10%, more preferably ±5%, or most preferably ±1% of the value with which the term is associated.

[0060] The term "substantially similar," when used to describe a comparison of diffraction patterns, means that the position of one or more peaks in degrees 2 theta, and the intensities of those peaks, may vary based on experimental variability due to the instrument used, the conditions under which the diffraction pattern was obtained, and impurities that may be present in the sample.

[0061] Where a range or ranges are specified for various numerical elements, unless otherwise specified, the range or ranges can be inclusive of the values.

[0062] The term "stochastic" refers to a property that is measured randomly, that is, it may have a random probability distribution or pattern that can be statistically analyzed but not precisely predicted.

[0063] A "molecular sieve" is a crystalline material with pores of molecular dimensions that allow the passage of molecules below a certain size. The term "molecular sieve" encompasses both zeolites and zeotypes. Zeolites are porous crystalline aluminosilicates, composed of TO4 tetrahedra (T=Si, Al) with O atoms connecting adjacent tetrahedra. Zeolites are materials with alumina and silicate frameworks, and include both aluminosilicates and metal-substituted aluminosilicates. Zeotypes are aluminophosphates (AlPO), metal-substituted aluminophosphates (MeAlPO), silicoaluminophosphates (SAPO), and metal-substituted silicoaluminophosphates. The term "molecular sieve" can also include mixtures of two or more of the above materials.

[0064] The term "framework type" is used in the sense given in "Atlas of Zeolite Framework Types", Sixth Revised Edition, Elsevier, 2007.

[0065] The basic or primary building unit (PBU) in the zeolite structure is the TO4 tetrahedron. Zeolite structure types can be described according to the structural building units in the framework, the pore openings and dimensions of the channel system, and the stacking of different polyhedral cage units. Structural building units, also known as secondary building units (SBUs), consist of tetrahedral units linked together in rings or cages by sharing a vertex for each pair of tetrahedra through nonlinear oxygen bridges. These SBUs are named based on the number of T atoms they contain, e.g., 6R for a six-membered ring, or double n-ring (e.g., double 6-ring, D6R) for a pair of rings. A three-dimensional framework can be built by assembling only one type of SBU. However, the structure of some zeolites is better described by using finite structural subunits (SSUs), i.e., sodalite or gmelinite cages, which are forms of polyhedra characterized by very complex symmetries. The SSUs represent structural features. Thus, in many cases, an SSU is not an SBU, because the skeleton cannot be constructed solely from SSUs. Often, SSUs need to share a corner, face, or edge to complete the skeleton. Another way to describe a cage in a skeleton structure is to describe it in terms of the rings that make up the faces of the cage, so that D6R is [4 6 6 2

[0036] Furthermore, many structures can be described in terms of layers stacked on top of each other, so-called infinite layers. SBU and SSU are not intended in themselves to describe the precursors from which zeolites grow, but may provide clues for selecting particular cations or structure directing agents suitable for favoring the formation of particular units and thus the desired framework structure.

[0066] A very important structural aspect in zeolites is the presence of cavities and channels connected to each other by windows to form a porous network within the structure. Pores are openings that extend from one side of the crystal to the other, but are not linear. Pores contain sections where the pore direction changes roughly multiple times, but still connect the two sides of the crystal. Cavities are polyhedral pores, with at least one face defined by a ring large enough to be penetrated by a compound with a size smaller than that of the ring, but do not extend infinitely (i.e., are not channels). Channels are pores that extend infinitely in one dimension and are large enough to allow guest species to diffuse along their length. Channels can intersect to form two- or three-dimensional channel systems. Windows have molecular sizes and can adsorb chemical species that are small enough to pass through them. One factor that controls the ability to adsorb molecules in zeolites is the size of the pore windows or openings. The cages are polyhedral pores whose windows are too narrow to allow the entry of guest species larger than HO, which means that the maximum size of a cage window is a six-membered ring.

[0067] The term "framework" refers to a corner-sharing network of tetrahedrally coordinated atoms. The term "structure" refers to both the framework and extra-framework components.

[0068] There are three distinct volumes associated with the scaffold: the total scaffold volume, the channel volume, and the cavity volume.

[0069] The term "extraframework" refers to materials, preferably metals, that are not located within the framework of the molecular sieve. The term "extraframework metal" refers to metals located on extraframework sites. The metal is from one of groups VB, VIIB, VIIB, VIIIB, IB, or IIB of the periodic table and is deposited on extraframework sites on the exterior surface or within channels, cavities, or cages of the molecular sieve. The metal may be in one of several forms, including, but not limited to, zero-valent metal atoms or clusters, isolated cations, mononuclear or polynuclear oxycations, or extended metal oxides.

[0070] The new intergrowth zeolites described herein are related to the ABC-6 family of structures, specifically those containing only double 6-rings (D6R) (http: / / europe.iza-structure.org / IZA-SC / intergrowth_families / ABC_6.pdf). The ABC-6 structure is built up from 6R with different stacking arrangements along one axis and connected by 4R. The 6R units can be centered at three different positions along the hexagonal ab plane: A (0,0,0), B (2 / 3,1 / 3,0) and C (1 / 3,2 / 3,0).

[0071] The molecular sieves described herein include intergrowths having cha-aft-"sfw-GME tails".

[0072] Activated molecular sieve refers to a molecular sieve comprising intergrowths having cha-aft-"sfw-GME tails" as described herein, where no structure directing agent is present in the molecular sieve.

[0073] Intergrowth molecular sieve phases are disordered planar intergrowths of the molecular sieve framework. See "Catalogue of Disordered Zeolite Structures", 2000 Edition, published by the Structure Committee of the International Zeolite Society, and "Collection of Simulated XRD Powder Patterns for Zeolites", Fifth Revised Edition, Elsevier, 2007, published on behalf of the Structure Committee of the International Zeolite Society, for a detailed description of intergrowth molecular sieve phases.

[0074] In a first aspect of the invention, molecular sieves are provided having an intergrowth comprising cha-aft-"sfw-GME tails" and one or more structure directing agents. These molecular sieves can be described as "as-made". All 6-rings are present as double 6-rings in these molecular sieves. The use of italics indicates that each aft cavity (aft) contains an associated gme cavity (gme) and each sfw cavity (sfw) contains two gme cavities. The cha and aft cavities are quoted in lower case and include the local AFX and AFT regions in the intergrowth. The term "sfw-GME" encompasses all cavities of sfw size and larger, including associated gme cavities. Intergrowths of CHA-GME have been described in the literature, but this does not imply the presence of a GME phase, but rather the range of cavity sizes up to the size of the molecular sieve particles. These molecular sieves containing this intergrowth are designated herein as JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D.

[0075] The molecular sieve can be an aluminosilicate or a metal substituted aluminosilicate, preferably an aluminosilicate. When the molecular sieve is an aluminosilicate, the silica to alumina ratio (SAR) can be about 20 or less, preferably 15 or less, more preferably 10 or less.

[0076] The molecular sieve can contain phosphorus in the framework and can be an aluminophosphate (AlPO), a metal substituted aluminophosphate (MeAlPO), a silicoaluminophosphate (SAPO), or a metal substituted silicoaluminophosphate.

[0077] The molecular sieve may contain one or more SDAs. The first SDA required (SDA-1) may be N,N-dimethyl-3,5-dimethylpiperidinium cation or N,N-diethyl-2,6-dimethylpiperidinium cation. The second SDA (SDA-2) that may be present is a CHA-generating SDA, such as trimethylammonylammonium cation, tetraethylammonium cation, trimethylbenzylammonium cation, trimethylcyclohexylammonium cation or trimethyl(cyclohexylmethyl)ammonium or phenyltrimethylammonium cation. A third SDA (SDA-3) that can be present is an AFX generating SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium)bis-1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane). The amount of SDA-2 and / or SDA-3 cations used can vary the proportion of cha-aft-"sfw-GME tails".

[0078] The molecular sieve of the first aspect of the invention may include at least one metal in the framework, the metal being selected from at least one of the metals of Groups IIIA, IB, IIB, VA, VIA, VIIA, VIIIA of the Periodic Table, and combinations thereof. Preferably, the metal is one or more of cerium, chromium, cobalt, copper, iron, magnesium, manganese, molybdenum, nickel, palladium, platinum, rhodium, titanium, tungsten, vanadium, and zinc. More preferably, the metal is one or more of cobalt, copper, iron, manganese, and zinc.

[0079] XRD analysis One of the characteristics of molecular sieves is their XRD pattern. XRD patterns of the SDA-containing molecular sieve of the first aspect of the invention and the activated molecular sieve of the second aspect of the invention were obtained using a Bruker D8 Advance equipped with a copper anode (X-ray wavelength 1.5406 A) and a LynxEye detector. The primary beam was fitted with a Goebels mirror and had a measurement circle of 280 mm, a slit of 0.22 mm and an axial solar of 2.5°. The secondary beam also had a measurement circle of 280 mm and an axial solar of 2.5°. There was no slit. Step-scanned data were collected between 3 and 100° 2theta with a step size of 0.022 at 1.5 steps / sec. The samples were rotated at 15 rpm. The collected data were analyzed with DIFFRAC.SUITE EVA Bruker software.

[0080] The relative intensity, 100xI / I0, where I0 is the intensity of the strongest line, i.e., the intensity of the peak, and the interplanar spacing d in angstroms corresponding to the recorded lines were calculated. Slight variations in the diffraction patterns of the SDA-containing intergrowths and activated molecular sieves in the tables or figures may also result from variations in the organic compounds used in the preparation, the presence of water in the samples, and variations in the molar ratio of Si to Al between samples. Despite these small fluctuations, the basic crystal structure of the SDA-containing intergrowths remains substantially unchanged. Similar variations can also be found in the X-ray diffraction patterns of the activated molecular sieve samples.

[0081] As will be appreciated by those skilled in the art, the determination of the parameter 2θ is subject to both human and mechanical errors, which, when combined, can impose an uncertainty of about ±0.2° on each reported value of 2θ. This uncertainty is, of course, also manifested in the reported values ​​of d-spacings calculated from the 2θ values. This imprecision is common throughout the art and does not prevent the present crystalline materials from being distinguished from one another and from prior art compositions. In some of the reported X-ray patterns, the relative intensities of the d-spacings are indicated by the symbols vs, s, m, and w, which represent very strong, strong, medium, and weak, respectively. In terms of relative intensity (100×I / I0), the above notation is defined as w (weak) being <20, m (medium) being ≧20 and <40, s (strong) being ≧40 and <60, and vs (very strong) being ≧60. When an intensity is near the end of a range, it can be characterized as spanning either range. For example, intensities from 18 to 22 may be listed as w to m, however, as is known in the art, due to variations in the intensity of the lines, one or more of the lines may have intensities within adjacent ranges.

[0082] In a second aspect of the invention, JMZ-11 and the four subgroups of the JMZ-11 family of molecular sieves described herein, namely JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D, are present in activated form. The term "activated" refers to a molecular sieve that has had two or more structure directing agents (SDAs) removed from the framework structure, or to one or more processes that can remove structure directing agents from a molecular sieve. Materials containing two or more SDAs can be activated by several processes known to those skilled in the art, for example, by calcination or treatment with peroxides.

[0083] The term "calcining" or "calcination" refers to heating a material in air, oxygen, or an oxygen-containing gas atmosphere. This definition is consistent with the IUPAC definition of calcination. (IUPAC. Compendium of Chemical Terminology, 2nd ed. (the "Gold Book"). Prepared by A.D. McNaught and A. Wilkinson. Blackwell Scientific Publications, Oxford (1997). XML online modified version: http: / / goldbook.iupac.org (2006-) constructed by M. Nic, J. Jirat, B. Kosata; update prepared by A. Jenkins. ISBN 0-9678550-9-8. doi:10.1351 / goldbook.) Calcination is performed to decompose metal salts, promote exchange of metal ions in the catalyst, and to adhere the catalyst to the substrate. The temperature used for calcination varies depending on the components in the material being calcined, and is generally from about 400° C. to about 900° C. for about 1 to 24 hours. In some cases, calcination can be carried out at temperatures up to about 1200° C. For applications involving the processes described herein, calcination is generally carried out at temperatures of from about 400° C. to about 700° C. for about 1 to 8 hours, preferably from about 400° C. to about 650° C. for about 1 to 4 hours.

[0084] In addition to removing the structure directing agent, it is preferred to remove any alkali or alkaline earth cations present. Preferably, the alkali or alkaline earth cations can be removed by treatment with an acid or ammonia solution. This ion exchange can be performed on SDA-containing intergrowths or on intergrowths that do not contain structure directing agents. The crystallinity of the material is better preserved when the alkali or alkaline earth cations are removed in the SDA-containing form.

[0085] One or more activated molecular sieves can be useful as catalysts in certain applications. The activated intergrowth is preferably calcined, but can also be used without calcination if the SDA is removed. The activated molecular sieve can be used either without metal exchange after synthesis or by metal exchange after synthesis, preferably by metal exchange after synthesis. Thus, in certain aspects of the invention, catalysts are provided that include activated molecular sieves that are free of any exchanged metals, in particular free or essentially free of exchanged or impregnated metals after synthesis. The term "essentially free" of exchanged metals means that the metals are present at <0.1 wt.%. The activated intergrowth preferably includes one or more catalytic metal ions by exchange or otherwise impregnation into the channels and / or cavities of the molecular sieve. Examples of metals that can be exchanged or impregnated after zeolite synthesis include transition metals such as copper, nickel, zinc, iron, tungsten, molybdenum, cobalt, titanium, zirconium, manganese, chromium, vanadium, niobium, tin, bismuth, antimony, noble metals such as platinum group metals (PGMs) such as ruthenium, rhodium, palladium, indium, platinum, and precious metals such as gold and silver; alkaline earth metals such as beryllium, magnesium, calcium, strontium, and barium; and rare earth metals such as lanthanum, cerium, praseodymium, neodymium, europium, terbium, erbium, ytterbium, and yttrium. Preferred transition metals for exchange after synthesis are base metals, and preferred base metals include those selected from the group consisting of manganese, iron, cobalt, nickel, copper, noble metals such as platinum group metals (PGMs) and mixtures thereof.

[0086] The transition metal can be present in an amount of about 0.1 to about 10 weight percent, e.g., about 0.1 to about 5 weight percent, about 0.1 to about 1.0 weight percent, about 2.5 to about 3.5 weight percent, and about 4.5 to about 5.5 weight percent, where the weight percent is based on the total weight of the molecular sieve material and the endpoints of the ranges can be included.

[0087] Particularly preferred exchange metals include calcium and / or cerium, especially in combination with calcium and / or cerium, and transition metals (T M ) and alkali metals (A M ) is about 15:1 to about 1:1, for example, about 10:1 to about 2:1, about 10:1 to about 3:1, or about 6:1 to about 4:1. M :A M Included, when present in a molar ratio, are copper and iron, where the endpoints of the ranges can be included.

[0088] Post-synthetic incorporated metals can be added to the molecular sieve by any known technique, such as ion exchange, impregnation, isomorphous substitution, and the like.

[0089] Metal-exchanged molecular sieves are distinct from metal-substituted molecular sieves because the exchanged metal cations are different from the metals that make up the molecular framework of the molecular sieve.

[0090] JMZ-11A The XRD pattern of SDA-containing JMZ-11A was measured from the sample of Example 1. The X-ray diffraction pattern is shown in Figure 1 and the peak values ​​are summarized in Table 1. Figure 1 shows the intensity normalized to 100% of the maximum peak height. This pattern and peak values ​​are characteristic of the SDA-containing JMZ-11 species.

[0091] When the molecular sieve is an aluminosilicate and the structure directing agent comprises N,N-dimethyl-3,5-dimethylpiperidinium cation, the powder XRD pattern of the hydrated aluminosilicate JMZ-11A can have characteristic lines of corresponding intensity, as shown in Table 1.

[0092] [Table 3]

[0093] The term "Rel. Int." (relative intensity) refers to the designation based on relative intensity (100 x I / I0), with the labels defined as w (weak) <20, m (moderate) ≥20 and <40, s (strong) ≥40 and <60, and vs (very strong) ≥60.

[0094] In a second aspect of the present invention, JMZ-11A is present in an activated form. The XRD pattern of activated JMZ-11A was measured from the sample of Example 1. The X-ray diffraction pattern is shown in Figure 2 and the peak values ​​are summarized in Table 2. Figure 2 shows the intensity normalized to 100% of the maximum peak height. The pattern and peak values ​​are characteristic of the activated JMZ-11 species.

[0095] [Table 4]

[0096] JMZ-11B The XRD pattern of SDA-containing JMZ-11B was measured from the sample of Example 2. The X-ray diffraction pattern is shown in Figure 3 and the peak values ​​are summarized in Table 3. Figure 3 shows the intensity normalized to 100% of the maximum peak height. This pattern and peak values ​​are characteristic of the SDA-containing JMZ-11B species.

[0097] When the molecular sieve is an aluminosilicate and the structure directing agent comprises N,N-diethyl-2,6-dimethylpiperidinium cation, the powder XRD pattern of the hydrated aluminosilicate JMZ-11B can have characteristic lines of corresponding intensity, as shown in Table 3.

[0098] [Table 5]

[0099] In a second aspect of the present invention, JMZ-11B is present in an activated form. The XRD pattern of activated JMZ-11B was measured from the sample of Example 2. The X-ray diffraction pattern is shown in Figure 4 and the peak values ​​are summarized in Table 4. Figure 4 shows the intensity normalized to 100% of the maximum peak height. The pattern and peak values ​​are characteristic of the species of activated JMZ-11B.

[0100] [Table 6]

[0101] JMZ-11C The XRD pattern of SDA-containing JMZ-11C was measured from the sample of Example 3. The X-ray diffraction pattern is shown in Figure 5 and the peak values ​​are summarized in Table 5. Figure 5 shows the intensity normalized to 100% for the maximum peak height. This pattern and peak values ​​are characteristic of the SDA-containing JMZ-11C species.

[0102] When the molecular sieve is an aluminosilicate and the structure directing agent includes N,N-dimethyl-3,5-dimethylpiperidinium cation and 1,3-bis(1-adamantyl)imidazolium cation, the powder XRD pattern of the hydrated aluminosilicate JMZ-11C can have characteristic lines of corresponding intensity, as shown in Table 5.

[0103] [Table 7]

[0104] In a second aspect of the present invention, JMZ-11C is present in an activated form. The XRD pattern of activated JMZ-11C was measured from the sample of Example 3. The X-ray diffraction pattern is shown in Figure 6 and the peak values ​​are summarized in Table 6. Figure 6 shows the intensity normalized to 100% of the maximum peak height. The pattern and peak values ​​are characteristic of the species of activated JMZ-11C.

[0105] [Table 8]

[0106] JMZ-11D The XRD pattern of SDA-containing JMZ-11D was measured from the sample of Example 4. The X-ray diffraction pattern is shown in Figure 7 and the peak values ​​are summarized in Table 7. Figure 7 shows the intensity normalized to 100% of the maximum peak height. This pattern and peak values ​​are characteristic of the SDA-containing JMZ-11B species.

[0107] When the molecular sieve is an aluminosilicate and the structure directing agent includes N,N-dimethyl-3,5-dimethylpiperidinium and trimethylammonidylammonium cations, the powder XRD pattern of the hydrated aluminosilicate JMZ-11D can have characteristic lines of corresponding intensity as shown in Table 7.

[0108] [Table 9]

[0109] In a second aspect of the present invention, JMZ-11D is present in an activated form. The XRD pattern of activated JMZ-11D was measured from the sample of Example 4. The X-ray diffraction pattern is shown in Figure 8 and the peak values ​​are summarized in Table 8. Figure 8 shows the intensity normalized to 100% of the maximum peak height. The pattern and peak values ​​are characteristic of the activated JMZ-11D species.

[0110] [Table 10]

[0111] How to Analyze Intergrowths The molecular sieves described herein represent a family of molecular sieves that include intergrowths of cha and aft with "sfw-GME tails", which are further defined below, and which are distinct from stochastic intergrowths of CHA and GME, such as babelite. They are also distinct from stochastic intergrowths of CHA and AFX or CHA and AFT, which do not have cavities larger than aft. The intergrowths described herein belong to the ABC-6 family of zeolites, specifically, only those zeolites with stacking sequences consisting exclusively of double 6-rings (D6R).

[0112] Intergrowths can form different structures within the bulk molecular sieve, which can result in the appearance of distinct phases that are recognized by XRD. The relative proportions of each intergrowth phase can be analyzed by X-ray diffraction, particularly by comparing the observed patterns to calculated patterns generated using algorithms to simulate the effects of stacking disorder.

[0113] DIFFaX is a Fortran computer program based on a mathematical model for calculating intensities from crystals containing planar faults (Treacy, MMJ; Newsam, JM; Deem, MW: A general recursion method for calculating diffracted intensities from crystals containing planar faults. Proc. R. Soc. London Ser. A 433 (1991) 499-520).

[0114] DIFFaX is a simulation program selected by and available from the International Zeolite Society to simulate powder XRD patterns of randomly intergrown phases (see "Collection of Simulated XRD Powder Patterns for Zeolites", Fifth Revised Edition, Elsevier, 2007, published on behalf of the Structure Committee of the International Zeolite Society). DIFFaX has been used to theoretically study zeolite beta (Treacy et al 1991), the AEI-CHA intergrowths in numerous patents, and many other intergrowths in zeolites and other materials.

[0115] Pure CHA has a three-dimensional pore system with CHA cavities connected by eight-ring windows that form eight-ring channels (Figure 10).

[0116] Pure GME has a three-dimensional pore system with GME cavities connected by 8 rings to 12 ring channels that run the entire length of the crystallite in the c-axis direction (Figure 11).

[0117] Intergrowths of CHA with GME are well known. In CHA-GME intergrowths, CHA units plug the ends of 12-ring channels, and the resulting GME units can have cavities (as well as associated gme cavities) in the direction of the c-axis that are as small as aft up to nearly the crystal length. The cavities in this system can be described using integers proportional to their length in the c-direction: 1=gme, 2=cha, 3=aft, 4=sfw, 5=”5”, 6=”6”, etc. Hereafter, we ignore gme cavities, as they are implicitly present in relation to the larger cavities (one per aft, two per sfw, three per “five”, etc., or (n-2) per “n” cavities, if n>2). The gme cavities provide a framework that connects the aft cavities and the larger cavities to each other in the basal plane direction. The CHA unit has a cavity of size 2, and the so-called GME in the intergrowth has a cavity size that can range from 3 to "infinity", depending on how quickly another defect closes the 12-ring channel.

[0118] The stochastic intergrowth model of the DIFFaX input shown in Figure 12 has individual layers 5 Angstroms thick, as listed in the CHA-GME file in the examples folder on Mike Treacy's DIFFaX website (http: / / www.public.edu / %7Emtreacy / DIFFaX.html). The basis of each layer is a top 6-ring ring of double 6-rings connected to the bottom 6-ring of an adjacent double 6-ring. The slash and backslash lines in the stacking schematic of Figure 13 represent the direction of this connection. For simplicity, the 6-rings have been omitted. In these ABC double 6-ring materials, the slashes indicate AB, BC, or CA stacking, and the backslashes indicate AC, CB, or BA stacking.

[0119] The CHA-GME intergrowths described in the literature are essentially stochastic intergrowths, with a single defect probability p describing the distribution of cavity sizes in the material. Analysis of this model leads to a monotonically decreasing subpopulation f of cavities with size n, one of which is fn+1 =pf n , for n ≥ 2, and f2 = (1-p) It is.

[0120] An example of this is given by Babelite with P=0.5 (R. Szostak, KP Lillerud, J. Chem. Soc., Chem. Commun. 1994, 2357). The range of the distribution as a function of p is shown in FIG.

[0121] In stochastic intergrowth, only the identity of the current layer determines the stacking probability of the next layer, and there is no memory effect of the previous layer. Treacy et al.'s paper includes the concept of memory or Reichweite to explain the clustering (or block intergrowth) of defects by including the effect of the previous layer on the next stacking probability (known as Reichweite 1). This is also shown in Figure 13. For example, when p is small, large blocks of CHA should alternate with large cavity-like GMEs.

[0122] The extension to Reichweite n, where the current layer and the previous n layers influence the next layer, is straightforward and has been described by H. Jagodzinski, Acta Cryst. 2 208-14 (1949). The essential features of the intergrowth in this application can be explained by the Reichweite 2 DIFFaX model (Figure 15). In the case of Reichweite 2, the stacking probability of a new layer in the crystallographic c-axis depends on the stacking of the previous two layers. The slashes and backslashes in brackets in Figure 15 indicate the stacking of the previous two layers. Layer type 1, followed by layer 1, is a CHA stacking sequence, and layer 3, followed by layer 6, are part of the GME sequence. This model directly considers only the framework and not the structure-directing agent molecules, but is nevertheless a reasonable descriptor.

[0123] This is because the Reichweite 2 DIFFaX model explicitly generates the cha, aft and sfw cavities, along with the gme cavities associated with aft and sfw. All known regular ABC-6, double 6-ring frameworks are included in the description of CHA, AFT, AFX and SFW. The stacking probabilities p, q, r and s are defined in the following 8x8 matrix, all with values ​​ranging from 0 to 1. The entry in row m of the matrix is ​​the probability that layer m is followed by the layer in column n. The layer arrangements and corresponding values ​​of stacking probabilities p, q, r and s for known regular phases are listed.

[0124] In the general case, the stacking probability gives the cavity size distribution f n It is easy to calculate and ignore the GME cavity since it is strictly related to the larger cavity (Figure 16).

[0125] If r=1, there are no cavities larger than sfw. If s=0, there are no sfw cavities and no "sfw-GME" tails. Thus, if r=1 and s=0, there is either a stochastic CHA-AFX intergrowth if q=(1-p), or a stochastic CHA-AFT intergrowth if q=1, although for the model, q need not be so constrained. Thus, the concept of cha-aft intergrowth includes local regions of CHA, AFT, and AFX.

[0126] If s>0, then the "sfw-GME" tail is present, f n+1 =pf n , but only if n>=4, The distribution is similar to that for stochastic CHA-GME, but with sfw rather than cha as the smallest cavity (ignoring the associated gme cavity). The probability r controls the length of the tail, i.e., how quickly the distribution drops off with increasing cavity size. As r approaches zero, the "sfw-GME" tail stretches into larger cavities. The population fraction of cha cavities is q / (p+q), the population fraction of aft cavities is p(1-s) / (p+q), and the population fraction of cavities in the "sfw-GME" tail is p / (p+q). Note that these fractions are independent of the probability r, which controls the tail length. The diffraction pattern, however, depends on these and on r.

[0127] However, if s=(1-r)=p and q=(1-p), these equations become f for n>=2. n+1 =pf n , decreasing to f2=(1-p). In this regime, there is no memory effect (Reichweite 0), which results in a stochastic CHA-GME intergrowth (Figure 17) in which the stacking probability of layers is independent of the previous stacking. The larger the value of p, the smaller the percentage of cha cavities and the larger the average non-gme cavity size, as shown in Figure 17. Note that when gme cavities are included, the average cavity size for all ABC-6 d6R materials (ordered or disordered) is exactly 2.

[0128] JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D are not stochastic intergrowths of CHA-GME. They are best described as cha-aft-"sfw-GME" intergrowths and can be explained by the Reichweite 2 model. The three materials contain a monotonically decreasing sfw-GME tail encompassing the range from the sfw cage to "infinity", but the cha and aft cages are in very different proportions for this tail compared to those in the stochastic CHA-GME intergrowths. The cage distributions in JMZ-11A, JMZ-11B, JMZ-11C and JMZ-11D, determined by the above analysis, are shown in Figures 18-21, respectively.

[0129] The use of lowercase cha and aft is to include local AFX and AFT regions in the intergrowth. Stochastic CHA-AFX intergrowths will necessarily have local regions of AFT, and there will be more AFT than AFX when the probability of CHA defects is small. However, CHA-AFT stochastic intergrowths will not have local regions of AFX, and the simulated X-ray diffraction (using DIFFaX) patterns will be different. Stochastic CHA-AFX and CHA-AFT intergrowths are subsets of the more general cha-aft intergrowth.

[0130] The "sfw-GME" tails are a significant part of the volume fraction in these cha-aft-"sfw-GME" intergrowths and cannot be neglected. CHA-AFT and CHA-AFX (or more generally cha-aft) intergrowths do not have such tails and no cavities larger than aft are present. The X-ray diffraction patterns of these cha-aft-"sfw-GME" materials cannot be approximated without the "sfw-GME" tails. Annular dark-field images recorded by aberration-corrected scanning transmission electron microscopy confirm this model.

[0131] Figures 22-25 show a comparison of the experimental XRD patterns of activated JMZ-11A, JMZ-11B, JMZ-11C, and JMZ-11D with DIFFaX simulations performed using the Reichweite 2 description. The figures show that the DIFFaX simulations performed using the Reichweite 2 description provide a good description of the intergrowth composition.

[0132] In the powder XRD patterns from the stochastic CHA-GME intergrowths, the 9.5° peak broadens and does not shift. In the JMZ-11 family, which includes JMZ-11A, JMZ-11B, JMZ-11C, and JMZ-11D, this peak shifts substantially away from 9.5°, but its broadening and the raised background between 7.7 and 13.1° are much greater than in the stochastic CHA-GME intergrowths (Figure 9). To properly simulate this for the dehydrated and activated samples, the sfw-GME tail must be included.

[0133] JMZ-11A comprises a structure directing agent (SDA-1) which is an N,N-dimethyl-3,5-dimethylpiperidinium cation, a cha cavity, an aft cavity and an "sfw-GME" tail, where the cha cavity is present in about 45 to about 65%, preferably about 54%, of the cavities in the "sfw-GME" tail, the aft cavity is present in about 18 to about 28%, preferably about 23%, of the cavities in the "sfw-GME" tail, and the remainder is present in about 7 to about 37%, preferably about 23%, of the larger cavities in the "sfw-GME" tail. The aft cavity and the gme cavity associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 35 to about 80%, preferably about 68%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11A has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0134] JMZ-11B comprises a structure directing agent (SDA-1) which is an N,N-diethyl-2,6-dimethylpiperidinium cation, a cha cavity, an aft cavity and an "sfw-GME" tail, where the cha cavity is present in about 55 to about 75%, preferably about 65%, of the cavities in the "sfw-GME" tail, the aft cavity is present in about 0 to about 10%, preferably about 5%, of the cavities in the "sfw-GME" tail, and the remainder is present in about 15 to about 45%, preferably about 30%, of the larger cavities in the "sfw-GME" tail. The aft cavity and the gme cavity associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 40 to 80%, preferably about 64%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11B has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0135] JMZ-11C contains two structure directing agents, N,N-dimethyl-3,5-dimethylpiperidinium cation and 1,3-bis(1-adamantyl)imidazolium cation, cha cavities, aft cavities and an "sfw-GME" tail, where the cha cavities are present in about 30 to about 45%, preferably about 39%, of the cavities in the "sfw-GME" tail, the aft cavities are present in about 45 to about 65%, preferably about 54%, of the cavities in the "sfw-GME" tail, and the remainder are present in about 2 to about 20%, preferably about 7%, of the larger cavities in the "sfw-GME" tail. The aft cavities and the gme cavities associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 5 to 45%, preferably about 23%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11C has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0136] JMZ-11D contains two structure directing agents, N,N-dimethyl-3,5-dimethylpiperidinium cation and trimethylamandylammonium cation, cha cavities, aft cavities and an "sfw-GME" tail, where the cha cavities are present in about 55 to about 75%, preferably about 65%, of the cavities in the "sfw-GME" tail, the aft cavities are present in about 7 to about 17%, preferably about 12%, of the cavities in the "sfw-GME" tail, and the remainder are present in about 8 to about 38%, preferably about 23%, of the larger cavities in the "sfw-GME" tail. The aft cavities and the gme cavities associated with the larger cavities are not included in these figures. The "sfw-GME" tail occupies about 50 to 90%, preferably about 75%, of the volume of the molecular sieve or molecular sieve particle. JMZ-11D has a monotonically decreasing distribution of cavity sizes, but cannot be explained as a stochastic CHA-GME intergrowth.

[0137] In a third aspect of the present invention, the catalyst comprises one or more activated H-form molecular sieves of the second aspect of the present invention described herein and further comprises at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn, preferably Cu, Fe, Co and Ni, more preferably Cu and Fe, most preferably Cu.

[0138] The activated H-form intergrowth in the catalyst can contain from about 0.1 to about 5 weight percent of at least one extraframework metal.

[0139] In a fourth aspect of the present invention, a catalyst article for treating exhaust gases comprises a catalyst comprising the activated H-form molecular sieve of the second aspect of the present invention, and further comprises at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn, preferably Co, Cu, Fe, and Ni, more preferably Cu and Fe, and most preferably Cu.

[0140] The activated H-form molecular sieve in the catalyst can contain from about 0.1 to about 5 weight percent of at least one extraframework metal.

[0141] The catalyst may be disposed on and / or within a porous substrate, preferably a flow-through filter or a wall-flow filter.

[0142] The catalyst of the present invention is particularly applicable to heterogeneous catalytic reaction systems (i.e., solid catalysts in contact with gaseous reactants). The catalyst can be disposed on and / or within a substrate, preferably a porous substrate, to improve contact surface area, mechanical stability, and / or fluid flow characteristics. A washcoat containing the catalyst can be applied to an inert substrate, such as a corrugated metal plate or a honeycomb cordierite brick. Alternatively, the catalyst can be kneaded with other ingredients, such as fillers, binders, and reinforcing agents, into an extrudable paste and then extruded through a die to form a honeycomb brick or extrudate, e.g., a cylinder, trilobe, or quadralobe. The catalyst can also be in the form of microspherical particles (10-150 microns in diameter) containing the activated molecular sieve of the present invention, along with fillers, binders, and / or reinforcing agents. The microspherical particles can be prepared by spray drying or other suitable techniques. Thus, the catalyst article can include the activated molecular sieve described herein coated on and / or incorporated into a substrate.

[0143] The catalyst article may include a washcoat comprising an activated molecular sieve as described in the second aspect of the present invention. The washcoat is preferably a solution, suspension, or slurry. Suitable coatings include a surface coating, a coating that penetrates a portion of the substrate, a coating that penetrates the substrate, or some combination thereof.

[0144] The washcoat may also include non-catalytic components such as fillers, binders, stabilizers, rheology modifiers, and other additives, including one or more of alumina, silica, non-zeolitic silica alumina, titania, zirconia, and ceria. When a catalyst is part of the washcoat composition, the washcoat may further include a binder containing Ce or ceria. When the binder contains Ce or ceria, the Ce containing particles in the binder are significantly larger than the Ce-containing particles in the catalyst. The catalyst composition may include pore formers such as graphite, cellulose, starch, polyacrylate, and polyethylene. These additional components do not necessarily catalyze the desired reaction, but instead improve the effectiveness of the catalyst material, for example, by increasing its operating temperature range, increasing the contact surface area of ​​the catalyst, increasing the adhesion of the catalyst to the substrate, etc. The washcoat loading on or in the substrate is about 0.3 g / in 3 ~ approx. 3.5g / in 3 where the endpoints of the range are inclusive. The loading can be a function of the type of substrate used and the backpressure resulting from the loading on a particular type of substrate. The lower limit for washcoat loading is 0.5 g / in 3 , 0.8g / in 3 , 1.0g / in 3 , 1.25g / in 3 , or 1.5g / in 3 The upper limit on washcoat loading is 3.5 g / in 3 , 3.25g / in 3 , 3.0g / in 3 , 2.75g / in 3 , 2.5g / in 3 , 2.25g / in 3 , 2.0g / in 3 , 1.75g / in 3 , or 1.5g / in 3 It can be.

[0145] Two of the most common substrate designs to which catalysts can be applied are plates and honeycombs. Preferred substrates, particularly for mobile applications, include flow-through monoliths having a so-called honeycomb shape, which are open at both ends and generally extend from the inlet face to the outlet face of the substrate, resulting in a high surface area to volume ratio and containing multiple adjacent parallel channels. In certain applications, honeycomb flow-through monoliths preferably have a high cell density, for example, about 600-800 cells per square inch, and / or an average inner wall thickness of about 0.18-0.35 mm, preferably about 0.20-0.25 mm. In certain other applications, honeycomb flow-through monoliths preferably have a low cell density, for example, about 150-600 cells per square inch, more preferably about 200-400 cells per square inch. Preferably, the honeycomb monoliths are porous. In addition to cordierite, silicon carbide, silicon nitride, ceramics, and metals, other materials that can be used for the substrate include aluminum nitride, silicon nitride, aluminum titanate, α-alumina, mullite, such as acicular mullite, pollucite, cermets, such as Al2OsZFe, Al2O3 / Ni, or B4CZFe, or composites containing segments of any two or more of these. Preferred materials include cordierite, silicon carbide, and alumina titanate.

[0146] Plate-type catalysts have lower pressure drop and are less likely to clog or plug than honeycomb types, which is advantageous for high efficiency stationary applications, but plate configurations can be much larger and more expensive. Honeycomb configurations are typically smaller than plate types, which is advantageous for mobile applications, but have higher pressure drop and clog more easily. The plate substrate can be made of metal, preferably corrugated metal.

[0147] A catalytic article can be made by the process described herein. The catalytic article can be made by a process that preferably includes applying a washcoat of an activated molecular sieve, preferably an extra-framework metal-containing activated molecular sieve, as a layer to a substrate, either before or after applying at least one additional layer of another composition for treating exhaust gas to the substrate. One or more catalytic layers, including a layer comprising an activated molecular sieve, are arranged on the substrate as sequential layers. As used herein, the term "sequential" with respect to catalytic layers on a substrate means that each layer is in contact with its adjacent layer and that the catalytic layers are generally arranged on top of one another on the substrate.

[0148] The activated molecular sieve catalyst can be disposed on the substrate as a first layer or zone, and another composition, such as an oxidation catalyst, a reduction catalyst, a capture component, or a NO x The storage component can be disposed as a second layer or zone on the substrate. As used herein, the terms "first layer" and "second layer" are used to describe the relative position of the catalyst layer within the catalyst article with respect to the normal direction of exhaust gas flow through and / or over the catalyst article. Under normal exhaust gas flow conditions, the exhaust gas contacts the first layer and then the second layer. The second layer can be applied to the inert substrate as a bottom layer, with the first layer being the top layer, which is applied over the second layer as a sequential series of sublayers.

[0149] After the exhaust gas has penetrated (and thus contacted) the first layer, it may contact the second layer and then pass back through the first layer and out of the catalyst component.

[0150] The first layer may be a first zone disposed on an upstream portion of the substrate, and the second layer is disposed on the substrate as a second zone, the second zone being downstream of the first zone.

[0151] A catalytic article can be produced by a process comprising applying an activated molecular sieve, preferably as a washcoat, to a substrate as a first zone, and then applying at least one additional composition for treating exhaust gases to the substrate as a second zone, where at least a portion of the first zone is downstream of the second zone. Alternatively, a composition comprising the activated molecular sieve can be applied to the substrate in a second zone downstream of the first zone containing the additional composition. Examples of the additional composition include an oxidation catalyst, a reduction catalyst, a capture component (e.g., sulfur, water, etc.), or NO. x Storage components include:

[0152] To reduce the amount of space required for an exhaust system, individual exhaust components can be designed to perform more than one function. For example, applying an SCR catalyst to a wall-flow filter substrate rather than a flow-through substrate allows one substrate to perform two functions: reducing NO in the exhaust gases. x The soot-removing filter helps reduce the overall size of the exhaust treatment system by aiding in catalytically reducing the concentration of soot and mechanically removing soot from the exhaust gas. The substrate can be a honeycomb wall-flow filter or a partial filter. Wall-flow filters are similar to flow-through honeycomb substrates in that they contain a plurality of adjacent parallel channels. However, the channels of a flow-through honeycomb substrate are open at both ends, whereas the channels of a wall-flow substrate are capped at one end, with the capping occurring in an alternating pattern at the ends of both adjacent channels. Capping alternating ends of the channels prevents gases entering the inlet face of the substrate from flowing in a straight line through the channels. Instead, exhaust gases enter the front of the substrate, travel to approximately the center of the channels, are forced through the channel walls, and then enter the back half of the substrate and exit the back of the substrate.

[0153] The substrate wall has a porosity and pore size that is gas permeable, but traps a large portion of particulate matter, such as soot, from the gas as it passes through the wall. A preferred wall-flow substrate is a high efficiency filter. Wall-flow filters for use in the present invention preferably have an efficiency of ≧about 70%, ≧about 75%, ≧about 80%, or ≧about 90%. The efficiency may be about 75 to about 99%, about 75 to about 90%, about 80 to about 90%, or about 85 to about 95%, where the efficiency is with respect to soot and other similarly sized particles, as well as particulate matter concentrations typically found in conventional diesel exhaust gases. For example, particulate matter in diesel exhaust may range in size from 0.05 microns to 2.5 microns. Thus, the efficiency may be based on this range, or on subranges such as 0.1 to 0.25 microns, 0.25 to 1.25 microns, or 1.25 to 2.5 microns.

[0154] Porosity is a percentage measure of void space in a porous substrate and is related to backpressure in an exhaust system; generally, the lower the porosity, the higher the backpressure. Preferably, the porous substrate has a porosity of about 30 to about 80%, e.g., about 40 to about 75%, about 40 to about 65%, or about 50 to about 60%, where the endpoints of the ranges can be included.

[0155] Pore ​​interconnectivity is measured as a percentage of the total void volume of the substrate and is the extent to which pores, voids, and / or channels join and form a continuous path through the porous substrate, i.e., from the inlet face to the outlet face. In contrast, pore interconnectivity is the sum of the closed pore volume and the volume of pores that have conduits on only one of the surfaces of the substrate. Preferably, the porous substrate has a pore interconnect volume of ≧about 30%, more preferably ≧about 40%.

[0156] The average pore size of the porous substrate is also important for filtration. The average pore size can be determined by any acceptable means, such as by mercury porosimetry. The average pore size of the porous substrate must be high enough to promote low back pressure while providing sufficient efficiency, either by the substrate itself, by promoting a soot cake layer on the surface of the substrate, or by a combination of both. Preferred porous substrates have an average pore size of about 10 to about 40 μm, e.g., about 20 to about 30 μm, about 10 to about 25 μm, about 10 to about 20 μm, about 20 to about 25 μm, about 10 to about 15 μm, and about 15 to about 20 μm.

[0157] In general, the manufacture of extruded solid bodies such as honeycomb flow-through or wall-flow filters containing the activated molecular sieves described herein as catalysts includes blending the activated molecular sieves, binders, optional organic thickening compounds into a homogenous paste, which is then added to one or more of the binder / matrix components or precursors thereof, and optionally stabilized ceria and inorganic fibers. The blend is compressed in a mixing or kneading device or extruder. The mixture has organic additives such as binders, pore formers, plasticizers, surfactants, lubricants, dispersants, etc., as processing aids to enhance wetting and thus produce a homogenous batch. The resulting plastic material is then molded, especially using an extrusion press or an extruder including an extrusion die, and the resulting molded body is dried and calcined. The organic additives are "burned out" during the calcination of the extruded solid body. The activated molecular sieve, catalytically active calcined product may also be washcoated or otherwise applied to the extruded solid body as one or more sublayers on the surface, or may be wholly or partially impregnated into the extruded solid body.

[0158] The binder / matrix component is preferably selected from the group consisting of cordierite, nitrides, carbides, borides, intermetallic compounds, lithium aluminosilicates, spinels, optionally doped aluminas, silica sources, titania, zirconia, titania-zirconia, zircon, and mixtures of any two or more thereof. The paste may optionally contain reinforcing inorganic fibers selected from the group consisting of carbon fibers, glass fibers, metal fibers, boron fibers, alumina fibers, silica fibers, silica-alumina fibers, silicon carbide fibers, potassium titanate fibers, aluminum borate fibers, and ceramic fibers.

[0159] The alumina binder / matrix component is preferably gamma alumina, but may be any other transition alumina, i.e., alpha alumina, beta alumina, chi alumina, eta alumina, p alumina, kappa alumina, theta alumina, delta alumina, lanthanum beta alumina, and mixtures of any two or more of such transition aluminas. The alumina is preferably doped with at least one non-aluminum element to enhance the thermal stability of the alumina. Suitable alumina dopants include silicon, zirconium, barium, lanthanides, and mixtures of any two or more of these. Suitable lanthanide dopants include La, Ce, Nd, Pr, Gd, and mixtures of any two or more of these.

[0160] Preferably, the activated molecular sieve is dispersed throughout, preferably evenly throughout, the extruded catalyst body.

[0161] If any of the above extruded solid bodies are made into a wall-flow filter, the porosity of the wall-flow filter may be 30-80%, for example 40-70%. Porosity as well as pore volume and pore radius can be measured, for example, using mercury intrusion porosimetry.

[0162] In a fifth aspect of the present invention, an exhaust system for treating exhaust gases from an engine includes (a) a catalyst article comprising the activated H-form molecular sieve of the second aspect of the present invention and at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn, preferably Cu, Fe, Co and Ni, more preferably Cu and Fe, most preferably Cu, disposed downstream from the engine, (b) a source of reducing agent such as ammonia or urea upstream of the catalyst article, and (c) an exhaust gas conduit for conveying exhaust gases from the engine to the catalyst article.

[0163] In some embodiments, the activated H-form molecular sieve of the second aspect of the present invention can be an SCR or ammonia oxidation component.

[0164] The system may be configured such that the catalyst is capable of producing NO at or above a desired efficiency at temperatures above 100°C, above 150°C, or above 175°C, etc. x A controller may be included for metering the nitrogenous reductant into the flowing exhaust gas only if it is determined that the reduction can be catalyzed. This determination may be aided by one or more suitable sensor inputs indicative of engine conditions selected from the group consisting of exhaust gas temperature, catalyst bed temperature, promoter position, exhaust gas mass flow rate in the system, manifold vacuum, ignition timing, engine speed, exhaust gas lambda value, amount of fuel injected into the engine, exhaust gas recirculation (EGR) valve position, and thus the magnitude of EGR and boost pressures.

[0165] In certain embodiments, the metering is direct (preferred NO x The control can be based on the amount of nitrogen oxides in the exhaust gas, which is measured either directly (using a sensor) or indirectly. Indirect determination can be based on, for example, a predicted NO xA pre-correlated look-up table or map stored in the control means is used that correlates any one or more of the above mentioned inputs with their content indicative of engine condition. The metering of nitrogenous reductant can be adjusted so that 60% to 200% of the theoretical ammonia is present in the exhaust gas entering the SCR catalyst, calculated at 1:1 NH3 / NO and 4:3 NH3 / NO2. The control means can comprise a pre-programmed processor such as an electronic control unit (ECU).

[0166] Exhaust systems for internal combustion engines are passive NO x The exhaust system preferably includes one or more additional aftertreatment devices capable of removing pollutants from the internal combustion engine exhaust gas at normal operating temperatures. Preferably, the exhaust system includes a passive NO x (1) a selective catalytic reduction (SCR) catalyst; (2) a particulate filter; (3) an SCR filter; and (4) a NO x and one or more other catalytic components selected from an adsorption catalyst, (5) a three-way catalyst, (6) an oxidation catalyst, or any combination thereof. x The adsorbent is preferably a separate component from any of the post-treatment devices described above. Alternatively, passive NO x The adsorbent may be incorporated as a component in any of the post-treatment devices described above.

[0167] These aftertreatment devices are well known in the art. Selective catalytic reduction (SCR) catalysts are used to reduce the amount of nitrogen compounds (e.g., ammonia or urea) or hydrocarbons (lean NO x By reacting with NO x to N2. Typical SCR catalysts consist of vanadia-titania catalysts, vanadia-tungsten-titania catalysts, or metal / zeolite catalysts such as iron / beta zeolite, copper / beta zeolite, copper / SSZ-13, copper / SAPO-34, Fe / ZSM-5, or copper / ZSM-5.

[0168] A particulate filter is a device that reduces particulate matter from the exhaust of an internal combustion engine. Particulate filters include catalyzed and bare particulate filters. Catalyzed particulate filters (for diesel and gasoline applications) contain metal and metal oxide components (e.g., Pt, Pd, Fe, Mn, Cu, and Ce) to oxidize hydrocarbons and carbon monoxide in addition to breaking down soot trapped by the filter.

[0169] Selective catalytic reduction filters (SCRFs) are single-substrate devices that combine the functionality of SCR with particulate filtering. They are used to remove NO from internal combustion engines. x and particulate matter emissions. In addition to the SCR catalyst coating, particulate filters can also contain other metal and metal oxide components (e.g., Pt, Pd, Fe, Mn, Cu, and ceria) to oxidize hydrocarbons and carbon monoxide in addition to breaking down soot trapped by the filter. NO x The adsorption catalyst (NAC) is x was adsorbed under lean exhaust conditions, and the adsorbed NO x was released under rich conditions, and the released NO x to form N2. NACs typically include a NOx storage component (e.g., Ba, Ca, Sr, Mg, K, Na, Li, Cs, La, Y, Pr, and Nd), an oxidizing component (preferably Pt), and a reducing component (preferably Rh). These components are contained on one or more supports.

[0170] Three-way catalysts (TWCs) typically x It is used in gasoline engines under stoichiometric conditions to convert CO to N2, carbon monoxide to CO2, and hydrocarbons to CO2 and H2O in a single unit.

[0171] Oxidation catalysts, particularly diesel oxidation catalysts (DOCS), are well known in the art. Oxidation catalysts are designed to oxidize CO to CO2 and the organic components (soluble organic components) of gas phase hydrocarbons (HC) and diesel particulate matter to CO2 and H2O. Typical oxidation catalysts include platinum and optionally also palladium on high surface area inorganic oxide supports such as alumina, silica-alumina, and zeolites.

[0172] The exhaust system is a passive NO x The adsorbent is located close to the engine and an additional aftertreatment device provides passive NO x The aftertreatment device can be configured to be located downstream of the adsorbent. Thus, under normal operating conditions, the engine exhaust gas is first subjected to passive NO absorption before contacting the aftertreatment device. x Alternatively, the exhaust system may be configured to allow the exhaust gas to pass through the adsorbent during low temperature periods (below temperatures in the range of about 150-220°C, preferably about 200°C, as measured at the aftertreatment device) to pass through the adsorbent. x The aftertreatment device may include a valve or other gas directing means so that the exhaust gas stream is directed into contact with the aftertreatment device before flowing to the adsorbent. Once the aftertreatment device reaches operating temperature (approximately 150-220° C., preferably 200° C., as measured at the aftertreatment device), the exhaust gas stream is then passed through a passive NO 2 sieve before contacting the aftertreatment device(s). x The NO is then redirected to contact the adsorbent. x The temperature of the adsorbent remains lower for a longer period, thus increasing the passive NO x The efficiency of the adsorbent is improved while allowing the aftertreatment device to reach operating temperature more quickly. U.S. Patent No. 5,656,244, the teachings of which are incorporated herein by reference, teaches, for example, a means for controlling exhaust gas flow during cold start and normal operating conditions.

[0173] In a sixth aspect of the present invention, a method for synthesizing the SDA-containing molecular sieve of the first aspect of the present invention comprises the steps of: a. forming a reaction mixture comprising: (i) at least one aluminum source; (ii) at least one silicon source; (iii) at least one alkali or alkaline earth cation source; and (iv) one or more structure directing agents; b. heating the reaction mixture; c. forming molecular sieve crystals having intergrowths and a structure directing agent as described herein; d. Recovering at least a portion of the molecular sieve crystals from the reaction mixture.

[0174] Many aluminum compounds and mixtures thereof are suitable for use as at least one source of alumina in the present invention. Aluminum compounds include, but are not necessarily limited to, aluminum oxide, boehmite, pseudoboehmite, aluminum hydroxychloride, aluminum alkoxides such as aluminum triisopropoxide, aluminum triethoxide, aluminum tri-n-butoxide, and aluminum triisobutoxide, and mixtures thereof. The preferred aluminum component is selected from the group consisting of aluminum hydroxide, boehmite, and pseudoboehmite.

[0175] The at least one source of aluminum can include aluminum alkoxides, aluminum phosphate, aluminum hydroxide, sodium aluminate, pseudoboehmite, hydrated alumina, organoalumina, colloidal alumina, zeolite Y, and mixtures thereof.

[0176] Some silicon compounds and their mixtures can be used as the silicon component for the method of the present invention.Silicon compounds include, but are not limited to, silica sol silica gel, colloidal silica, fumed silica, silicic acid, tetraethyl silicate, tetramethyl silicate, alkoxide, silicate, tetraalkyl orthosilicate, aqueous colloidal suspension of silica, and their mixtures.Preferred silicon components include materials selected from the group consisting of silica sol, silica gel, colloidal silica, fumed silica, silicic acid, and their mixtures.

[0177] The source of alkali or alkaline earth cations may be any source of these elements, and is preferably selected from sources of Na, K, and combinations thereof.

[0178] SDA-1 is an N,N-dimethyl-3,5-dimethylpiperidinium cation or an N,N-diethyl-2,6-dimethylpiperidinium cation. SDA-2 is a CHA-generating SDA, such as the trimethyladmandylammonium cation. SDA-3 is an AFX-generating SDA, such as the 1,3-bis(1-adamantyl)imidazolium cation. SDA-2 and / or SDA-3 can be added to control the ratio of cha to aft, and thus the "sfw-GME tail."

[0179] The cation of the structure directing agent can be associated with an anion selected from the group consisting of acetate, bicarbonate, bromide, carbonate, carboxylate, chloride, fluoride, hydroxide, iodide, sulfate, and tetrafluoroborate, or combinations thereof. Preferably, the anion is hydroxide.

[0180] The reaction mixture may have the following molar composition:

[0181] [Table 11] where Me is Si, Ge, Sn, Ti or a combination thereof and is calculated to be in the oxide form (MO2), A is Al, Fe, Cr, B, Ga or a combination thereof and is calculated to be in the oxide form (A2O3), X is Na, K or a combination thereof and is calculated to be in the oxide form (X2O), and [OH - is calculated as the sum of hydroxide ions contributed by all components, SDA-1 is N,N-dimethyl-3,5-dimethylpiperidinium cation or N,N-diethyl-2,6-dimethylpiperidinium cation, SDA-2 is CHA-generating SDA, e.g., trimethyladmandylammonium cation, tetraethylammonium cation, trimethylbenzylammonium cation, trimethylcyclohexylammonium cation or trimethyl(cyclohexylmethyl)ammonium or phenanthylammonium cation. and SDA-3 is an AFX-generated SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

[0182] The reaction mixture can further comprise from about 0.1 to about 10% w / w of seed crystals, which include crystalline molecular sieves having an AEI, AFX, AFT, CHA, GME, or SFW skeleton and / or intergrowths having a JMZ-11, JMZ-11B, or JMZ-11C skeleton.

[0183] The solvent can be mixed with the structure directing agent before it is added to the reaction mixture. Preferably, the structure directing agent is completely miscible with the solvent or soluble in the solvent. Suitable solvents include, but are not necessarily limited to, water, methanol, ethanol, n-propanol, isopropanol, C4 alcohols, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and mixtures thereof. A preferred solvent includes water.

[0184] The silica component can be mixed in a suitable solvent to form a first mixture of uniform composition and texture. Sufficient mixing, stirring, or agitation can usually be used. The aluminum component can be added to this mixture, followed by the structure directing agent.

[0185] To produce an SDA-containing intergrowth, the molar ratios of the components in the mixture must be controlled and maintained. Prior to exposure to conditions effective to produce the molecular sieve product, the final reaction mixture, excluding any other organic or inorganic moieties or species that may be present, has the following molar composition ratios:

[0186] [Table 12] where Me is Si, Ge, Sn, Ti or a combination thereof and is calculated to be in the oxide form (MO2), A is Al, Fe, Cr, B, Ga or a combination thereof and is calculated to be in the oxide form (A2O3), X is Na, K or a combination thereof and is calculated to be in the oxide form (X2O), and [OH -is calculated as the sum of hydroxide ions contributed by all components, SDA-1 is N,N-dimethyl-3,5-dimethylpiperidinium cation or N,N-diethyl-2,6-dimethylpiperidinium cation, SDA-2 is CHA-generating SDA, e.g., trimethyladmandylammonium cation, tetraethylammonium cation, trimethylbenzylammonium cation, trimethylcyclohexylammonium cation or trimethyl(cyclohexylmethyl)ammonium or phenanthylammonium cation. and SDA-3 is an AFX-generated SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

[0187] Sufficient mixing, blending, stirring, or agitation is preferably used to provide a uniform composition throughout the mixture. The use of concentration or composition gradients should be minimized, as such gradients may result in the formation of different molecular sieve products.

[0188] Preferably, a constant temperature can be maintained during the preparation of the mixture. Cooling or heating may be required to provide a constant temperature environment. Suitable temperatures for the preparation of the mixture can range from about 15°C to about 80°C, preferably from about 20°C to about 50°C. Pressure is usually not critical for the preparation of the mixture unless one or more gases are used to control other reaction parameters such as pH, temperature, or concentration.

[0189] Preferably, the overall process has an overall yield on silica of at least about 60%, such as at least about 70%, such as at least about 80%.

[0190] The reaction mixture may be in the form of a solution, a colloidal dispersion (colloidal sol), a gel, or a paste, with a gel being preferred.

[0191] Generally, the reaction mixture can be maintained at an elevated temperature until the SDA-containing intergrowth crystals form. Hydrothermal crystallization is usually carried out under autogenous pressure at a temperature of about 100 to about 220° C., e.g., about 150 to 200° C., for several hours, e.g., about 0.1 to about 10 days, preferably about 1 to about 7 days.

[0192] During the hydrothermal crystallization process, intergrowth crystals can be allowed to spontaneously nucleate from the reaction mixture. The use of intergrowth crystals as seed material can be advantageous in reducing the time required for complete crystallization to occur. When used as seeds, the intergrowth crystals can be added in an amount of 0.1 to 10% of the weight of silica used in the reaction mixture.

[0193] Once the SDA-containing intergrowth crystals are formed, the solid product can be separated from the reaction mixture by standard separation techniques such as filtration. The SDA-containing intergrowth crystals can be washed with water and then dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for flash drying) or for a few hours (e.g., about 4 to 24 hours for oven drying at 75 to 150° C.) to obtain the SDA-containing intergrowth crystals. The drying step can be carried out at atmospheric pressure or under vacuum.

[0194] It will be understood that the order of the foregoing steps, and each of the time and temperature values ​​set forth above, are merely exemplary and may be varied.

[0195] Intergrowth crystals produced according to the methods described herein can have an average crystal size of about 0.01 to about 20 μm, e.g., about 0.01 to about 5 μm, about 0.2 to about 1 μm, and about 0.25 to about 0.5 μm, where the end points of the ranges are included. Larger crystals can be milled using a jet mill or other particle-to-particle comminution technique to an average size of about 1.0 to about 1.5 microns to facilitate washcoating the catalyst-containing slurry onto a substrate, such as a flow-through monolith.

[0196] The reaction mixture for the intergrowth synthesis process typically contains at least one aluminum source, at least one structure directing agent (SDA-1), which includes N,N-dimethyl-3,5-dimethylpiperidinium cation or N,N-diethyl-2,6-dimethylpiperidinium cation, at least one silicon source, and at least one alkali metal or alkaline earth metal source. The composition can further include a second SDA (SDA-2) and / or a third SDA (SDA-3). SDA-2 is a CHA-generating SDA, such as trimethylamandyl ammonium cation, tetraethyl ammonium cation, trimethyl benzyl ammonium cation, trimethyl cyclohexyl ammonium cation, or trimethyl (cyclohexylmethyl) ammonium or phenyl trimethyl ammonium cation.

[0197] SDA-3 is an AFX generating SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

[0198] The synthesis methods described herein are not necessarily limited to forming metalloaluminosilicates, but may also be applied to synthesize other compositions of JMZ-11, such as molecular sieves that contain phosphorus in the framework, such as aluminum phosphates (AlPO), metal substituted aluminophosphates (MeAlPO), silicoaluminophosphates (SAPO), or metal substituted silicoaluminophosphates.

[0199] In a seventh aspect of the present invention, a method is described for the synthesis of an activated molecular sieve from an activated molecular sieve containing SDA. The activated molecular sieve lacks the structure directing agent present in the activated molecular sieve of the first aspect of the present invention. The activated molecular sieve can be calcined or treated with peroxide to remove the SDA.

[0200] The activated molecular sieve can be produced by calcining an intergrowth containing two or more SDAs at a temperature and time sufficient to remove the structure directing agent and form an activated molecular sieve. The activated molecular sieve can be calcined at 300-700°C, preferably 400-650°C, in the presence of an oxygen-containing gas (e.g., air) when it is desired to oxidize the SDA. In some cases, when a reducing environment is preferred, the calcination is performed using an inert gas. The inert gas can be any gas that is substantially free of oxygen (less than 1% oxygen by volume, preferably less than 0.1% oxygen by volume), most preferably any gas that is free of oxygen. Preferably, the inert gas is nitrogen, argon, neon, helium, carbon dioxide, and the like, and mixtures thereof. Calcination is preferably performed for more than one hour.

[0201] Producing the activated molecular sieve of the second embodiment conventionally can include first forming the SDA-containing intergrowth of the first embodiment of the invention and then converting the SDA-containing intergrowth to the activated molecular sieve.

[0202] In an eighth embodiment of the present invention, the composition for producing SDA-containing intergrowths comprises the following materials in the corresponding proportions:

[0203] [Table 13] where Me is Si, Ge, Sn, Ti or a combination thereof and is calculated to be in the oxide form (MO2), A is Al, Fe, Cr, B, Ga or a combination thereof and is calculated to be in the oxide form (A2O3), X is Na, K or a combination thereof and is calculated to be in the oxide form (X2O), and [OH - is calculated as the sum of hydroxide ions contributed by all components, SDA-1 is N,N-dimethyl-3,5-dimethylpiperidinium cation or N,N-diethyl-2,6-dimethylpiperidinium cation, SDA-2 is CHA-generating SDA, e.g., trimethyladmandylammonium cation, tetraethylammonium cation, trimethylbenzylammonium cation, trimethylcyclohexylammonium cation or trimethyl(cyclohexylmethyl)ammonium or phenanthylammonium cation. and SDA-3 is an AFX-generated SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

[0204] Some silicon compounds and their mixtures can be used as the silicon component for the composition of the present invention.Silicon compounds include but are not limited to silica sol silica gel, colloidal silica, fumed silica, silicic acid, tetraethyl silicate, tetramethyl silicate, and their mixtures.Preferred silicon components include materials selected from the group consisting of silica sol, silica gel, colloidal silica, fumed silica, silicic acid, and their mixtures.

[0205] Many aluminum compounds and mixtures thereof are suitable for use as the aluminum component of the present invention. Aluminum compounds include, but are not necessarily limited to, aluminum oxide, boehmite, pseudoboehmite, aluminum hydroxychloride, aluminum alkoxides such as aluminum triisopropoxide, aluminum triethoxide, aluminum tri-n-butoxide, and aluminum triisobutoxide, and mixtures thereof. Preferred aluminum components are selected from the group consisting of aluminum hydroxide, boehmite, and pseudoboehmite.

[0206] The composition includes a first SDA (SDA-1) and can further include a second SDA (SDA-2) and / or a third SDA (SDA-3). SDA-1 is an N,N-dimethyl-3,5-dimethylpiperidinium cation or an N,N-diethyl-2,6-dimethylpiperidinium cation. SDA-2 is a CHA-generating SDA, such as the trimethyladamantylammonium cation, the tetraethylammonium cation, the trimethylbenzylammonium cation, the trimethylcyclohexylammonium cation, or the trimethyl(cyclohexylmethyl)ammonium or phenyltrimethylammonium cation, and SDA-3 is an AFX-generating SDA, such as 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

[0207] The anion associated with the cation can be acetate, bicarbonate, bromide, carbonate, carboxylate, chloride, fluoride, hydroxide, iodide, sulfate, and tetrafluoroborate, or combinations thereof. Preferably, the anion is hydroxide.

[0208] The composition may further comprise from about 0.1 to about 10% w / w of seed crystals comprising crystalline molecular sieves having an AEI, AFX, AFT, CHA, GME or SFW framework and / or intergrowths having a JMZ-11, JMZ-11B or JMZ-11C framework.

[0209] In a ninth aspect of the present invention, there is provided a method for making an activated molecular sieve from a molecular sieve comprising an intergrowth containing an SDA of the first aspect of the present invention and an alkali metal cation. It is usually desirable to remove the alkali metal cation by ion exchange and replace it with hydrogen, ammonium, or any desired metal ion. Thus, the zeolite of the present invention may be a Na-type zeolite, a K-type zeolite, or a combination of Na,K-type, etc., an H-type zeolite, an ammonium-type zeolite, or a metal-exchanged zeolite. A typical ion exchange technique involves contacting the synthetic zeolite with a solution containing a salt of the desired replacing cation. A wide variety of salts can be used, with chlorides and other halides, nitrates, sulfates, and carbonates being particularly preferred. Representative ion exchange techniques are well known in the art. The ion exchange is performed after synthesis, and can be performed either before or after calcining the zeolite. After contact with the salt solution of the desired replacing cation, the zeolite is typically washed with water and dried at a temperature ranging from 65° C. to about 315° C., usually from 80° C. to 150° C. After washing, the zeolite can be calcined in an inert gas and / or in air at a temperature ranging from about 315° C. to 850° C. for 1 to 48 hours or more to produce a catalytically active and stable product.

[0210] In a tenth aspect of the present invention, there is provided a method for treating exhaust gas from an engine by contacting the exhaust gas with an activated molecular sieve according to the second aspect of the present invention hereinbefore. The method comprises removing NO 2 from the gas. x The gas can be used for the reduction of compounds and / or the oxidation of NH3 by mixing the gas with an activated molecular sieve or a metal-containing activated molecular sieve and NO in the gas. x and contacting for a time sufficient to reduce the concentration of the compound.

[0211] The method for treating exhaust gases is x and / or NH3-containing combustion exhaust gas is contacted with the activated H-form molecular sieve described herein to produce NO x to N2 and H2O, and / or oxidizing at least a portion of the NH3.

[0212] NO x The combustion exhaust gas containing NO is treated with a passive NO 2 sieve containing the activated H-type molecular sieve described herein. x A method for treating an exhaust gas comprising contacting the exhaust gas with an absorbent.

[0213] The combustion exhaust gas containing NH3 is passed through a passive NO filter containing the activated H-type molecular sieve described herein. x A method for treating an exhaust gas comprising contacting the exhaust gas with an absorbent.

[0214] The activated molecular sieve or metal-containing activated molecular sieve can promote the reaction of a reducing agent, preferably ammonia, with nitrogen oxides to selectively form elemental nitrogen (N2) and water (H2O). Thus, the catalyst can be formulated to favor the reduction of nitrogen oxides by the reducing agent (i.e., SCR catalyst). Examples of such reducing agents include hydrocarbons (e.g., C3-C6 hydrocarbons), and nitrogenous reducing agents such as ammonia and ammonia hydrazine, or any suitable ammonia precursor such as urea ((NH2)2CO), ammonium carbonate, ammonium carbamate, ammonium bicarbonate, or ammonium formate.

[0215] Activated molecular sieves, or metal-containing activated molecular sieves, can also promote the oxidation of ammonia. Preferably, the activated molecular sieve contains one or more metal ions, such as copper or iron, impregnated therein. The catalyst can be formulated to favor the oxidation of ammonia with oxygen, particularly the concentrations of ammonia typically found downstream of an SCR catalyst (e.g., an ammonia oxidation (AMOX) catalyst, such as an ammonia slip catalyst (ASC)). The activated molecular sieve, or metal-containing activated molecular sieve, can be disposed as an upper layer over an oxidizing lower layer, the lower layer comprising a platinum group metal (PGM) catalyst or a non-PGM catalyst. Preferably, the catalyst components in the lower layer are disposed on a high surface area support, including, but not limited to, alumina.

[0216] The SCR and AMOX operations can be carried out in series, with both processes utilizing a catalyst comprising an activated molecular sieve or a metal-containing activated molecular sieve as described herein, and the SCR process being carried out upstream of the AMOX process, for example, the SCR formulation of the catalyst can be disposed on the inlet side of a filter and the AMOX formulation of the catalyst can be disposed on the outlet side of the filter.

[0217] Therefore, NO in the gas xA method for reducing a compound or oxidizing NH3 in a gas, comprising: x The NO x A method is disclosed that includes contacting a gas with the catalyst composition described herein for catalytic reduction of a compound. The catalyst article can have an ammonia slip catalyst disposed downstream of a selective catalytic reduction (SCR) catalyst. The ammonia slip catalyst can oxidize at least a portion of any nitrogenous reductant not consumed by the selective catalytic reduction process. The ammonia slip catalyst can be disposed on the outlet side of a wall-flow filter, and the SCR catalyst can be disposed upstream of the filter. The ammonia slip catalyst can be disposed on a downstream end of a flow-through substrate, and the SCR catalyst can be disposed on an upstream end of the flow-through substrate. The ammonia slip catalyst and the SCR catalyst can be disposed on separate bricks in the exhaust system. These separate bricks can be adjacent and in contact with each other, or can be separated by a certain distance, provided that they are not in fluid communication with each other, and provided that the SCR catalyst brick is not disposed upstream of the ammonia slip catalyst brick.

[0218] The SCR process and / or the AMOX process may be carried out at a temperature of ≧100°C, preferably from about 150°C to about 750°C, more preferably from about 175°C to about 550°C, and even more preferably from 175°C to 400°C.

[0219] In some conditions the temperature range can be 450-900° C., preferably 500-750° C., more preferably 500-650° C., even more preferably 450-550° C. Temperatures above 450° C. are particularly useful for the treatment of exhaust gases from large and small diesel engines equipped with exhaust systems containing (optionally catalyzed) diesel particulate filters which are actively regenerated, for example by injection of hydrocarbons into the exhaust system upstream of the filter, and where the molecular sieve catalyst for use in the present invention is located downstream of the filter.

[0220] The method of the present invention comprises contacting an exhaust gas with one or more flow-through SCR catalytic devices in the presence of a reductant to remove NO in the exhaust gas. x and (b) preferably reducing the concentration of soot by the inlet of the catalytic filter and the subsequent steps of: (a) accumulating and / or burning the soot in contact with the inlet of the catalytic filter; x and (c) introducing a nitrogenous reductant into the exhaust gas stream and then contacting the nitrogenous reductant with a catalytic filter without an intervening catalytic step involving treatment of the reductant. x Adsorption catalyst or lean NO x The process may include one or more of the following steps: generating NH3 on the trap, preferably using such NH3 as a reductant in a downstream SCR reaction; (d) contacting the exhaust gas stream with a DOC to oxidize hydrocarbon soluble organic components (SOF) and / or carbon monoxide to CO2 and / or NO to NO2, which in turn are used to oxidize particulate matter in a particulate filter and / or reduce particulate matter (PM) in the exhaust gas; and (e) contacting the exhaust gas with an ammonia slip catalyst, preferably downstream of the SCR catalyst, to oxidize most, if not all, of the ammonia before venting the exhaust gas to the atmosphere or passing the exhaust gas through a recirculation loop and then allowing / re-entering the exhaust gas into the engine.

[0221] All or at least a portion of the nitrogen-based reductant, particularly NH3, for consumption in the SCR process can be delivered to an SCR catalyst, such as an SCR catalyst of the present invention disposed on a wall-flow filter, using a NO x Adsorption catalyst (NAC), lean NO x Trap (LNT) or NO xThe NAC component may be provided by a storage / reduction catalyst (NSRC). NAC components useful in the present invention include catalysts of combinations of basic materials (such as alkali metals, alkaline earth metals, or rare earth metals, including alkali metal oxides, alkaline earth metal oxides, and combinations thereof) and precious metals (such as platinum), and optionally reduction catalyst components such as rhodium. Specific types of basic materials useful for NAC include cesium oxide, potassium oxide, magnesium oxide, sodium oxide, calcium oxide, strontium oxide, barium oxide, and combinations thereof. The precious metals are preferably present in an amount of about 10 to about 200 g / ft 3 , e.g. 20~60g / ft 3 Alternatively, the precious metal of the catalyst is present at about 40 to about 100 grams per cubic foot. 3 The average concentration of the mixture may be:

[0222] During periodic rich regeneration events, NH3 and NO x It can be generated on an adsorption catalyst. NO x The SCR catalyst downstream of the adsorption catalyst reduces NO x In a combined system, the SCR catalyst can store the NH3 released from the NAC catalyst during rich regeneration events and use the stored NH3 to reduce the NOx that passes through the NAC catalyst during normal lean operating conditions. x is selectively reduced in part or in whole.

[0223] The exhaust gas treatment method described herein can be carried out on exhaust gases from combustion processes, such as exhaust gases from internal combustion engines (either mobile or stationary), gas turbines, and coal or oil fired power plants. The method can also be used to treat gases from industrial processes such as smelting, such as refinery heaters and boilers, furnaces, chemical processing industries, coke ovens, municipal waste plants, and incinerators. The method can be used to treat exhaust gases from lean-burn internal combustion engines of vehicles, such as diesel engines, lean-burn gasoline engines, or engines powered by liquid petroleum gas or natural gas.

[0224] The method for treating exhaust gas comprises converting a combustion exhaust gas containing NOx into a passive NOx catalyst comprising an activated molecular sieve according to the second aspect of the present invention as described hereinabove. x The method may further include contacting the NO with an absorbent. x is adsorbed at low temperatures and the adsorbed NO x Passive NO is effective at releasing NO at temperatures above low temperatures. x The adsorbent may comprise a precious metal and an activated molecular sieve. The precious metal may be selected from the group consisting of platinum, palladium, rhodium, gold, silver, iridium, ruthenium, osmium, and mixtures thereof, preferably palladium.

[0225] Passive NO x The adsorbent is adapted to adsorb NO at or below low temperatures (preferably below 250°C, more preferably at about 200°C). x At temperatures above low, the adsorbed NO x can be effective in releasing passive NO x The adsorbent comprises a precious metal and an activated molecular sieve. The precious metal is selected from the group consisting of palladium, platinum, rhodium, gold, silver, iridium, ruthenium, osmium, or mixtures thereof; more preferably, palladium, platinum, rhodium, or mixtures thereof. Palladium is particularly preferred.

[0226] Passive NO x The adsorbent can be prepared by any known means. For example, a noble metal can be added to an activated molecular sieve to passively adsorb NO by any known means. x The adsorbent can be formed and the method of addition is not believed to be particularly important. For example, precious metal compounds (e.g., palladium nitrate) can be supported on activated molecular sieves by impregnation, adsorption, ion exchange, incipient wetness, precipitation, etc. Other metals can also be supported on activated molecular sieves by passive NO x The adsorbent can be added to the adsorbent. Preferably, passive NO x A portion of the precious metals in the adsorbent (greater than 1 percent of the total precious metals loaded) is located inside the pores of the activated molecular sieve. More preferably, greater than 5 percent of the total amount of precious metals is located inside the pores of the activated molecular sieve, and even more preferably, greater than 10 percent, or greater than 25%, or greater than 50 percent of the total amount of precious metals can be located inside the pores of the activated molecular sieve.

[0227] Preferably, passive NO x The sorbent further comprises a flow-through substrate or a filter substrate. x The adsorbent is coated onto a flow-through or filter substrate, preferably deposited onto the flow-through or filter substrate using a washcoat procedure, to provide passive NO x A sorbent system can be produced.

[0228] The flow-through substrate or filter substrate can be a substrate capable of containing catalytic components. The substrate is preferably a ceramic substrate or a metal substrate. The ceramic substrate can be made of any suitable refractory material, such as alumina, silica, titania, ceria, zirconia, magnesia, molecular sieve, preferably zeolite, more preferably aluminosilicate, silicon nitride, silicon carbide, zirconium silicate, magnesium silicate, aluminosilicate, metalloaluminosilicate (such as cordierite and spodumene), or any two or more mixtures or mixed oxides thereof. Cordierite, magnesium aluminosilicate, and silicon carbide are particularly preferred.

[0229] The metal substrate can be made of any suitable metal, particularly heat-resistant metals and metal alloys such as titanium and stainless steel, and ferritic alloys containing iron, nickel, chromium, and / or aluminum in addition to other trace metals.

[0230] The flow-through substrate is preferably a flow-through monolith having a honeycomb structure with many small parallel thin-walled channels that are axially continuous through the substrate and extend entirely from the inlet or outlet of the substrate. The channel cross-section of the substrate can be any shape, but is preferably square, sinusoidal, triangular, rectangular, hexagonal, trapezoidal, circular, or elliptical.

[0231] The filter substrate is preferably a wall-flow monolith filter. The channels of the wall-flow filter are alternately blocked. This allows the exhaust gas flow to enter the channels through an inlet, then flow through the channel walls and exit the filter through a different channel that leads to an outlet. Thus, particulate matter in the exhaust gas flow is trapped within the filter.

[0232] Passive NO x The sorbent can be added to the flow-through or filter substrate by any known means. A washcoat procedure can be used to deliver passive NOx A representative process for preparing the adsorbent is described below. It will be understood that the following process may be modified according to different embodiments of the present invention.

[0233] Preformed passive NO x The sorbent can be added to the flow-through or filter substrate by a washcoating process. Alternatively, passive NO x The adsorbent can be formed on a flow-through or filter substrate by first wash-coating an unmodified small pore molecular sieve onto the substrate to produce a molecular sieve-coated substrate. The activated molecular sieve-coated substrate can then be loaded with a precious metal, which can be accomplished by an impregnation procedure or the like.

[0234] The washcoating procedure preferably involves the use of passive NO x This is accomplished by first slurrying finely divided particles of the adsorbent (or unmodified small pore molecular sieve) in a suitable solvent, preferably water, to form a slurry. Additional components, such as transition metal oxides, binders, stabilizers, or promoters, may also be incorporated into the slurry as a mixture of water-soluble or water-dispersible compounds. The slurry preferably contains a solids content of 10 to 70 weight percent, more preferably 20 to 50 weight percent. Prior to forming the slurry, passive NO x The adsorbent (or unmodified small pore molecular sieve) particles are preferably subjected to a size reduction process (eg, milling) such that the average particle size of the solid particles is less than 20 microns in diameter.

[0235] The flow-through or filter substrate can then be dipped into the slurry one or more times to deposit the desired loading of catalytic material on the substrate, or the slurry can be coated onto the substrate. If the activated molecular sieve does not have a precious metal incorporated therein prior to washcoating the flow-through or filter substrate, the activated molecular sieve coated substrate is typically dried and calcined, and then the precious metal can be added to the molecular sieve coated substrate by any known means, including, for example, impregnation, adsorption, or ion exchange, with a precious metal compound (e.g., palladium nitrate). Preferably, the entire length of the flow-through or filter substrate is free of any passive NO ions. x A washcoat of the adsorbent is coated with the slurry to cover the entire surface of the substrate.

[0236] Flow-through or filter substrate passive NO x After coating with the adsorbent and optionally impregnating with a precious metal, the coated substrate is preferably dried and then calcined by heating at an elevated temperature to produce passive NO x A substrate coated with the adsorbent is formed. Preferably, the calcination is carried out at 400-600° C. for about 1-8 hours.

[0237] Flow-through or filter substrates are passive NO x In this case, passive NO x The sorbent can be extruded to form a flow-through or filter substrate. x The adsorbent extruded substrate is preferably a honeycomb flow-through monolith.

[0238] Extruded molecular sieve substrates and honeycomb bodies, as well as processes for making them, are known in the art. See, for example, U.S. Pat. Nos. 5,492,883, 5,565,394 and 5,633,217, and U.S. Pat. No. Re. 34,804. Typically, the molecular sieve material is mixed with a permanent binder, such as a silicone resin, and a temporary binder, such as methylcellulose, and the mixture is extruded to form a green honeycomb body, which is then fired and sintered to form the final small pore molecular sieve flow-through monolith. The molecular sieve can contain precious metals prior to extrusion, thereby allowing passive NOx to be produced by the extrusion procedure. x Adsorbent monoliths are produced. Alternatively, passive NO x To produce an adsorbent monolith, a precious metal can be added to a preformed molecular sieve monolith.

[0239] The present invention also relates to a passive NO 2 ion exchanger comprising an activated molecular sieve, as described herein above. x Also included is a method for treating exhaust gas from an internal combustion engine using an adsorbent. The method comprises the steps of: x Passive NO x Adsorption onto an adsorbent and passive NO at temperatures above the above temperature x NO from the adsorbent x and passive NO x Desorbed NO on a catalytic component downstream of the adsorbent x and catalytically removing

[0240] Passive NO x The catalytic components downstream of the adsorbent are SCR catalysts, particulate filters, SCR filters, NO x It can be an adsorption catalyst, a three-way catalyst, an oxidation catalyst, or a combination thereof.

[0241] In an eleventh aspect of the present invention, there is provided a process for converting methanol to olefins (MTO) by contacting ethanol with an activated H-type molecular sieve comprising an intergrowth of the second aspect of the present invention described herein.

[0242] In an eleventh aspect of the present invention, there is provided a method for converting oxygenates such as methanol to olefins (MTO) by contacting methanol with an activated molecular sieve of the second aspect of the present invention described hereinabove. Reaction processes for the conversion of oxygenates to olefins (OTO) are known in the art. Specifically, in an OTO reaction process, an oxygenate is contacted with a molecular sieve catalyst composition under conditions effective to convert at least a portion of the oxygenate to light olefins. When methanol is the oxygenate, the process is generally referred to as a methanol to olefins (MTO) reaction process. Methanol is a particularly preferred oxygenate for the synthesis of ethylene and / or propylene.

[0243] The process for converting an oxygenate feedstock to light olefin products includes: a) providing an oxygenate feedstock comprising a majority of methanol; b) providing a catalyst composition comprising an activated molecular sieve and optionally a basic metal oxide co-catalyst; and c) contacting the oxygenate feedstock with the catalyst composition under conditions sufficient to convert at least a portion of the oxygenate feedstock to light olefin products.

[0244] Oxygenate feedstocks, particularly mixed alcohol compositions containing methanol and ethanol, are useful feedstocks for various catalytic processes, particularly oxygenate to olefins (OTO) reaction processes, and can be converted to light olefin products, e.g., containing, preferably comprising, ethylene and / or propylene, using a catalyst composition, typically a primary oxide catalyst having at least two of Al, Si, and P (e.g., an aluminosilicate molecular sieve, preferably a high silica aluminosilicate molecular sieve), preferably a basic metal oxide cocatalyst. The olefins can then be recovered and used for further processing, e.g., in the production of polyolefins, such as polyethylene and / or polypropylene, olefin oligomers, olefin copolymers, mixtures thereof, and / or blends thereof.

[0245] One or more additional components can be included in the feedstock for the OTO reaction system. For example, the feedstock for the OTO reaction system may optionally contain, in addition to methanol and ethanol, one or more aliphatic-containing compounds, such as alcohols, amines, carbonyl compounds, such as aldehydes, ketones, and carboxylic acids, ethers, halides, mercaptans, sulfides, and the like, and mixtures thereof. The aliphatic portion of the aliphatic-containing compound typically contains 1 to 50 carbon atoms, preferably 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, and most preferably 1 to 4 carbon atoms.

[0246] Non-limiting examples of aliphatic-containing compounds include alcohols such as methanol, ethanol, n-propanol, isopropanol, and the like, alkyl mercaptans such as methyl mercaptan and ethyl mercaptan, alkyl sulfides such as methyl sulfide, alkyl amines such as methyl amine, alkyl ethers such as DME, diethyl ether, and methyl ethyl ether, alkyl halides such as methyl chloride and ethyl chloride, alkyl ketones such as dimethyl ketone, alkyl aldehydes such as formaldehyde and acetaldehyde, and various organic acids such as formic acid and acetic acid.

[0247] The various raw materials mentioned above are mainly converted into one or more olefins. The olefins or olefin monomers produced from the raw materials typically have 2-30 carbon atoms, preferably 2-8 carbon atoms, more preferably 2-6 carbon atoms, even more preferably 2-4 carbon atoms, and most preferably ethylene and / or propylene. Non-limiting examples of olefin monomers include ethylene, propylene, butene-1, pentene-1,4-methyl-pentene-1, hexene-1, octene-1, and decene-1, preferably ethylene, propylene, butene-1, pentene-1,4-methyl-pentene-1, hexene-1, octene-1, and isomers thereof. Other olefin monomers can include, but are not limited to, unsaturated monomers, diolefins having 4-18 carbon atoms, conjugated or non-conjugated dienes, polyenes, vinyl monomers, and cyclic olefins.

[0248] A catalytic article for converting low molecular weight oxygen-containing species to an olefin-rich hydrocarbon stream can include an activated molecular sieve, the activated molecular sieve being disposed on a support and / or within a structure.

[0249] A catalytic article for converting low molecular weight oxygen-containing species to an aromatics-rich hydrocarbon stream can include an activated molecular sieve, the activated molecular sieve being disposed on a support and / or within a structure.

[0250] The catalyst may be incorporated with or mixed with other additive materials. Such mixtures are typically referred to as formulated catalysts or catalyst compositions. Preferably, the additive materials are substantially inert to conversion reactions involving dialkyl ethers (e.g., dimethyl ether) and / or alkanols (e.g., methanol, ethanol, etc.).

[0251] One or more other materials can be mixed with the activated molecular sieve, particularly materials that are resistant to the temperatures and other conditions used in organic conversion processes. Such materials can include catalytically active and inactive materials, as well as synthetic or naturally occurring zeolites, and inorganic materials such as clays, silica, and / or other metal oxides, such as alumina. The latter can be either naturally occurring or in the form of gel precipitates or gels including mixtures of silica and metal oxides. The use of catalytically active materials can facilitate the conversion and / or selectivity of the catalyst in oxygenate conversion processes. Inactive materials can advantageously serve as diluents and control the amount of conversion in the process, thereby allowing economical and regular product production without the use of other means to control the reaction rate. These materials can be incorporated into naturally occurring clays, such as bentonite and kaolin, to improve the crush strength of the catalyst under commercial operating conditions. Materials (e.g., clays, oxides, etc.) can function as binders for the catalyst. Since it is desirable to prevent the catalyst from breaking down into powder-like materials in commercial use, it may be desirable to provide a catalyst with good crush strength.

[0252] Naturally occurring clays that can be used include, but are not limited to, the montmorillonite and kaolin families, including sub-bentonites and kaolins commonly referred to as Dixie clays, McNamee clays, Georgia clays, and Florida clays, or others whose primary mineral constituents include halloysite, kaolinite, dickite, nacrite, or anauxite. Such clays can be used in their raw state, as originally mined, or as initially calcined, acid-treated, or chemically modified. Other useful binders can include, but are not limited to, inorganic oxides such as silica, titania, beryllia, alumina, and mixtures thereof.

[0253] In addition to the materials mentioned above, the activated molecular sieves can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, and silica-titania, as well as ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.

[0254] The relative proportions of activated molecular sieve and inorganic oxide matrix can vary widely, for example, the mixture may contain a zeolite content ranging from about 1 to about 90 weight percent, more usually from about 2 to about 80 weight percent of the composite, especially when the composite is prepared in the form of beads.

[0255] The present invention also relates to C2, C3, C4 and C5 products formed by the application of OTO or MTO using activated molecular sieves as catalysts or co-catalysts.

[0256] The following examples demonstrate, but do not limit, aspects of the present invention. EXAMPLES

[0257] Example 1 - Synthesis of SDA-containing JMZ-11A, with approximately 54% cha cavities, 23% aft cavities, and 23% "sfw-GME" tails. 7.27 g of sodium hydroxide (98%) was dissolved in 51.5 g of demineralized water in a polypropylene bottle under stirring. 27.42 g of commercial USY powder (Al2O3=17.44 wt%, SiO2=55.89 wt%, Na2O=0.08 wt%) was added to the resulting solution to form a white homogeneous slurry. Next, 26.23 g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (R A 0.0 ... A The resulting synthesis gel, corresponding to the Molgel formula of OH-300H2O, was stirred for 30 minutes and then placed in a 0.6 L stirred autoclave for crystallization at 120° C. After 68 hours of crystallization, the solid product was collected and dried in an oven at 120° C. Characteristic XRD data for the sample of Example 1 is shown in Table 9 below.

[0258] [Table 14]

[0259] The as-prepared powder of Example 1 was directly ion-exchanged by applying four cycles of contact with ammonium acetate (10 g of solution per gram of zeolite powder, 10% 15 ammonium acetate, 80° C. and 1 hour per ion-exchange cycle). After drying in an oven at 120° C., the directly ion-exchanged product was calcined in a muffle furnace by increasing the temperature to 550° C. at a ramp rate of 1.0° C. per minute to remove SDA species. After 6 hours of calcination, the resulting powder was subjected to two additional cycles of ion-exchange with ammonium acetate to remove residual sodium from the zeolite powder. After removing sodium by ion-exchange, the solid product was again dried at 120° C. and calcined at 550° C. by the same procedure. The X-ray diffraction data of the product is shown in FIG. 1 and Table 10. The SAR (silica to alumina ratio) of the resulting zeolite was 7.1 as measured by XRF.

[0260] [Table 15]

[0261] Example 2 - Synthesis of SDA-containing JMZ-11B with approximately 65% ​​cha cavities, 5% aft cavities, and 30% "sfw-GME" tails. 13.18 g of sodium hydroxide (98%) was dissolved in 40.0 g of demineralized water in a polypropylene bottle under stirring. 28.30 g of commercial USY powder (Al2O3=17.44 wt%, SiO2=55.89 wt%, Na2O=0.08 wt%) was added to the resulting solution to form a white homogeneous slurry. The mixture was then poured in turn with 32.9 g of 1,1-diethyl-2,6-dimethylpiperidinium hydroxide solution (22.0% concentration in water) followed by 288.5 g of sodium silicate solution (Na2O wt%=9.00 wt%, SiO2=28.8 wt%). 34.0SiO2-1.00Al2O3-12.0Na2O-0.80R CThe resulting synthesis gel, corresponding to the Molgel formula of OH-290H2O, was stirred for 30 minutes and then placed in a 0.6 L stirred autoclave for crystallization at 120° C. After 21 hours of crystallization, the solid product was collected and dried in an oven at 120° C. The XRD data is shown in Table 11 below.

[0262] [Table 16]

[0263] The as-prepared powder of Example 2 was ion-exchanged and calcined as described in Example 1. X-ray diffraction data for the product is shown in Figure 2 and Table 12. The SAR of the resulting zeolite was 6.2 as measured by XRF.

[0264] [Table 17]

[0265] Example 3 - Synthesis of SDA-containing JMZ-11C with approximately 39% cha cavities, 54% aft cavities, and 7% "sfw-GME" tail. 27.35 g of commercial USY powder (Al2O3=17.44 wt%, SiO2=55.89 wt%, Na2O=0.08 wt%) was combined with 45.77 g of demineralized water in a polypropylene bottle under stirring to form a white homogeneous slurry. To the solution, 24.42 g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide solution (55.8% concentration in water) and 8.29 g of 1,3-bis(1-adamantyl)imidazolium hydroxide (20.0% concentration in water) were added. 7.39 g of NaOH (98%) and 288.4 g of sodium silicate solution (Na2O wt%=9.00 wt%, SiO2=28.8 wt%) were poured in sequence into the mixture. 35.0SiO2-1.00Al2O3-11.0Na2O-1.40R A OH-0.10R BThe resulting synthesis gel, corresponding to the Molgel formula of OH-300H2O, was kept stirring for 30 minutes and then placed in a 0.6 L stirred autoclave for crystallization at 120° C. After 24 hours of crystallization, the solid product was collected and dried in an oven at 120° C. The XRD data is shown in Table 13 below.

[0266] [Table 18]

[0267] The as-prepared powder of Example 3 was ion-exchanged and calcined as described in Example 1. X-ray diffraction data of the product is shown in Figure 4 and Table 14. The SAR of the resulting zeolite was 8.0 as measured by XRF.

[0268] [Table 19]

[0269] Example 4 - Synthesis of SDA-containing JMZ-11D with approximately 65% ​​cha cavities, 12% aft cavities, and 23% "sfw-GME" tails. 7.27 g of sodium hydroxide (98%) was dissolved in 45.7 g of demineralized water in a polypropylene bottle under stirring. 27.41 g of commercial USY powder (Al2O3=17.44 wt%, SiO2=55.89 wt%, Na2O=0.08 wt%) was added to the resulting solution to form a white homogeneous slurry. The mixture was then poured in turn with 26.23 g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide solution (55.8% concentration in water), 5.83 g of trimethylamandylammonium hydroxide (0.51% concentration in water), and then 289.2 g of sodium silicate solution (Na2O wt%=9.00 wt%, SiO2=28.8 wt%). 35.0SiO2-1.00Al2O3-11.0Na2O-1.50R A OH-0.003R BThe resulting synthesis gel, corresponding to the Molgel formula of OH-300H2O, was kept stirring for 30 minutes and then placed in a 0.6 L stirred autoclave for crystallization at 120° C. After 64 hours of crystallization, the solid product was collected and dried in an oven at 120° C. The XRD data is shown in Table 15 below.

[0270] [Table 20]

[0271] The as-prepared powder of Example 4 was ion-exchanged and calcined as described in Example 1. X-ray diffraction data of the product is shown in Figure 8 and Table 16. The SAR of the resulting zeolite was 7.3 as measured by XRF.

[0272] [Table 21]

[0273] Example 5 - Preparation of Cu catalyst for SCR Calcined JMZ-11A from Examples 1, 2, 3 and 4 were impregnated with copper at a loading of 3.33 wt.% using the required amount of copper(II) acetate monohydrate (Shepherd) dissolved in demineralized water. The impregnated samples were dried at 80° C. overnight and then calcined at 550° C. in air for 4 h. A reference sample of BEA with SAR 28 was prepared following the same method as above.

[0274] A sample of the powder catalyst was pelletized to provide a fresh catalyst, and then a portion of the fresh catalyst was hydrothermally aged in a flow of 10% HO in air using the following procedure: the sample was heated in air only to 250° C. at a rate of 10° C. / min. The sample was then heated in 10% HO in air at a rate of 10° C. / min to 750° C. After holding at a temperature of 750° C. for 80 hours, the sample was cooled in a steam / air mixture until the temperature was <250° C., and then air only was flowed over the sample until the air had cooled to approximately room temperature.

[0275] Example 6 - Standard NH3SCR catalyst test 500 ppm NO x Fresh and aged pelletized samples of powdered catalyst were tested in an apparatus where a gas containing (NO only), 500 ppm NH3, 14% O2, 4.6% H2O, 5% CO2, with the balance N2, flows over the catalyst at a space velocity of 90 K / h. The samples were heated from room temperature to 150°C under the gas mixture described above, except for NH3. At 150°C, NH3 was added to the gas mixture and the samples were held under these conditions for 30 min. The temperature was then ramped from 150°C to 500°C at 5°C / min.

[0276] NO x The results of the conversion activity profile are shown in Figures 26 and 27. The fresh sample of Example 1 produced 1% to 15% higher NO than the benchmark BEA.Cu in the temperature range of 340°C to 550°C. x It was found that Examples 2, 3 and 4 all exhibited 1% to 15% higher NO conversion levels than the benchmark BEA.Cu in the temperature range of 275°C to 550°C (Figure 26). x After aging (FIG. 27), Examples 3 and 4 showed 5-65% higher NO conversion than BEA.Cu over the entire test temperature range of 150-550° C. x After aging, Examples 1 and 2 showed the conversion level of NO in BEA.Cu in the temperature range of 275 to 450 °C. x Conversion levels were 2-20% higher than those shown in Examples 1, 2, 3 and 4. Thus, when utilized in the optimum operating temperature range, NO x It has been demonstrated that this offers important advantages in conversion.

[0277] The NO concentration in the gas passing through the fresh catalyst and the aged catalyst over the temperature range of 150°C to 500°C is shown in Figure 28. The gas flowing into the device contains only NO and NO xThe levels of NO produced by Examples 1, 2, 3, and 4 were all significantly lower (peak value of about 5 ppm) over the entire temperature range than that of BEA (peak values ​​of about 55 ppm and 28 ppm). After aging (FIG. 29), the levels of NO produced by BEA were significantly reduced over the entire temperature range, with peak values ​​of about 11 ppm and about 18 ppm. However, the aged samples of Examples 1, 2, 3, and 4 all showed higher NO over most of the temperature range. x Conversion was also observed, but still with lower levels of NO compared to BEA over the entire temperature range. Thus, Examples 1, 2, 3, and 4 all show significant advantages over BEA in terms of NO production in both the fresh and aged states.

Claims

1. A molecular sieve comprising a first structure directing agent (SDA-1), cha cavities, aft cavities and an "sfw-GME" tail, the molecular sieve having a monotonically decreasing distribution of cavity sizes, wherein SDA-1 comprises N,N-dimethyl-3,5-dimethylpiperidinium cations or N,N-diethyl-2,6-dimethylpiperidinium cations, the cha cavities are present in 30-75% of the cavities in the tail, the aft cavities are present in 0-65% of the cavities in the tail, and the remainder are larger cavities that are 2-45% of the cavities in the "sfw-GME" tail, the molecular sieve being an aluminosilicate.

2. 2. The molecular sieve of claim 1, wherein SDA-1 comprises N,N-dimethyl-3,5-dimethylpiperidinium cations, the cha cavities are present in 45-65% of the cavities in the tail, the aft cavities are present in 18-28% of the cavities in the tail, and the remainder are larger cavities which are 7-37% of the cavities in the "sfw-GME" tail.

3. 2. The molecular sieve of claim 1, wherein SDA-1 comprises N,N-diethyl-2,6-dimethylpiperidinium cations, the cha cavities are present in 55-75% of the cavities in the tail, the aft cavities are present in 0-10% of the cavities in the tail, and the remainder are larger cavities which are 15-45% of the cavities in the "sfw-GME" tail.

4. 2. The molecular sieve of claim 1, wherein SDA-1 comprises an N,N-dimethyl-3,5-dimethylpiperidinium cation, the molecular sieve further comprises a 1,3-bis(1-adamantyl)imidazolium cation, the cha cavities are present in 30-45% of the cavities in the tail, the aft cavities are present in 45-65% of the cavities in the tail, and the remainder are larger cavities which are 2-20% of the cavities in the "sfw-GME" tail.

5. 2. The molecular sieve of claim 1, wherein SDA-1 comprises N,N-dimethyl-3,5-dimethylpiperidinium cation, the molecular sieve further comprises trimethyladmandylammonium cation, the cha cavities are present in 55-75% of the cavities in the tail, the aft cavities are present in 7-17% of the cavities in the tail, and the remainder are larger cavities which are 8-38% of the cavities in the "sfw-GME" tail.

6. 1. An activated H-form molecular sieve comprising cha cavities, aft cavities and an "sfw-GME" tail having a monotonically decreasing distribution of cavity sizes, wherein the cha cavities are present in 30-75% of the cavities in the tail, the aft cavities are present in 0-65% of the cavities in the tail, and the remainder are larger cavities which are 2-45% of the cavities in the "sfw-GME" tail, the activated H-form molecular sieve is free of SDA, and the activated H-form molecular sieve is an aluminosilicate.

7. 7. The molecular sieve of claim 1 or claim 6, wherein the molecular sieve comprises at least one metal in the framework, the metal being selected from at least one of the metals of groups IIIA, IB, IIB, VA, VIA, VIIA, and VIIIA of the periodic table, and combinations thereof.

8. 7. The activated H-form molecular sieve of claim 6, wherein the molecular sieve further comprises at least one extraframework metal selected from the group consisting of Ag, Au, Ce, Co, Cr, Cu, Fe, Ga, In, Ir, Mn, Mo, Ni, Os, Pd, Pt, Re, Rh, Ru, Sn and Zn.

9. A catalyst comprising the activated H-form molecular sieve of claim 6.

10. 10. The catalyst of claim 9, wherein the activated H-form molecular sieve contains from 0.1 to 5 weight percent of at least one extraframework metal.

11. A catalytic article for treating exhaust gases comprising the catalyst according to claim 9 or claim 10, wherein the catalyst is disposed on and / or within a honeycomb structure.

12. The following ingredients in the corresponding proportions: 【Table 1】 wherein Me is Si, Ge, Sn, Ti or a combination thereof, and is in the oxide form (MO 2 ), where A is Al, Fe, Cr, B, Ga or a combination thereof, in the oxide form (A 2 O 3 ) where X is Na, K or a combination thereof and is in the oxide form (X 2 O), and [OH - ] is calculated as the sum of hydroxide ions contributed by all components, SDA-1 is an N,N-dimethyl-3,5-dimethylpiperidinium cation or an N,N-diethyl-2,6-dimethylpiperidinium cation; SDA-2 is selected from the group consisting of trimethylammonidylammonium cation, tetraethylammonium cation, trimethylbenzylammonium cation, trimethylcyclohexylammonium cation, trimethyl(cyclohexylmethyl)ammonium and phenyltrimethylammonium cation; SDA-3 is a composition selected from the group consisting of 1,3-bis(1-adamantyl)imidazolium, 1,1-(butane-1,4-diyl)bis-(quinuclidin-1-ium), 1,1-(pentane-1,5-diyl)bis-(quinuclidin-1-ium), and 1,1'-(1,4-butanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane), 1,1'-(1,5-pentanediyl)bis(4-aza-1-azoniabicyclo[2.2.2]octane).

13. A method for synthesizing the molecular sieve of claims 1 to 5, comprising: a. forming a reaction mixture comprising: (i) at least one aluminum source, (ii) at least one silicon source, (iii) at least one alkali or alkaline earth cation source, and (iv) one or more structure directing agents; b. heating the reaction mixture; c. forming molecular sieve crystals having intergrowths and the structure directing agent by hydrothermal crystallization; and d) recovering at least a portion of said molecular sieve crystals from said reaction mixture.

14. NO x and / or NH 3 A combustion exhaust gas containing NO is contacted with the activated H-type molecular sieve of claim 6 to produce NO x At least a part of 2 and H 2 Selective reduction to O and / or NH 3 23. A method for treating an exhaust gas comprising oxidizing at least a portion of

15. NO x A combustion exhaust gas containing x A method for treating an exhaust gas comprising contacting the exhaust gas with an absorbent.

16. 10. A process for converting methanol to olefins (MTO), comprising contacting methanol with the activated H-form molecular sieve of claim 6.

Citation Information

Patent Citations

  • Cabassite-containing molecular sieves, their synthesis and their use in the conversion of eusigenates to olefins

    JP2007516152A

  • Disordered molecular sieve support for selective catalytic reduction of NOx

    JP2013522011A

  • Synthesis of AEI zeolite

    JP2016538217A

  • Copper-promoted gmelinite and use thereof in the selective catalytic reduction of no x

    WO2017211237A1

  • Novel disordered abc-6 molecular sieve

    WO2018086975A1